Decoding microplastic pollution in China freshwater: interpretable machine learning insights into composition-specific distribution and associated phthalate ester leaching risk - Xizhe Wan; Qiong Guo; Zhenfei Han; Tianqi Jiang; Guangshuo Chai; Yindong Tong; Hongyang Cui; Xiaoyu Cui (Water Research, 2026)

Looking beyond appearances: The influence of threat-based awe on preferences for suboptimal food - Tingyi Wang; Feifan Cai; Han Zhao; Xiaoyu Wan (Food Quality and Preference, 2026)

Green extractive desalination with natural deep eutectic solvents - Ping Keung Wong; Lok Wan Ng; Wei Han; Matthew Y. Lui (Desalination, 2026)

Response patterns of soil protist communities to long-term nitrogen addition and increased precipitation - Yaru Nie; Jiajia Zhang; Binghai Lei; Zhongjie Sun; Junqiang Zheng; Yanyan Yu; Shiqiang Wan; Shijie Han (Soil Ecology Letters, 2026)

Improving multi-view video fusion and model generalization in pig behavior monitoring with teacher–student semi-supervised learning - Shuo Wan; Junkai Li; Feiyue Xue; Tao Han; Ying Sha; Li Qin (Computers and Electronics in Agriculture, 2026)

Saebias A–G, eudesmane sesquiterpenes from Salvia plebeia with potential for Alzheimer's disease prevention via anti-neuroinflammatory and neuroprotective effects - Xiao-Die Shu; Han-Fei Liu; Yu-Qiong Liao; Wan-Jun Pu; Ting Zhao; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Cadmium-associated cognitive impairment in adults: Proteomics-guided blood-based risk stratification with external validation and rat multimodal corroboration - Hao Gao; Hui Liu; Sheng Wan; Zhaokui Dan; Jianjun Xiong; Zelong Xing; Yinghui Yin; Feng Han; Yong Yang; Maoqin Tian; Qiwen Chen; Zhijian Hu; et al. (Environmental Pollution, 2026)

Bending-dominated chiral metastructures with tunable thermal expansion: Planar-to-cylindrical design and dual-mechanism modeling - Siyuan Chen; Bin Han; Peiyuan Zheng; Zhaoxing Zhang; Shiguang Wan; Qi Zhang (Engineering Structures, 2026)

Bioinspired peptidomimetics combat bacterial resistance via “trap-and-kill” strategy by self-assembly into bacteria-responsive nanonets - Yuhang He; Jie Su; Panpan Wang; Muhammad Subaan Fareed; Yaqi Lu; Zhaopeng Wang; Min Li; Daicao Wan; Feiyun Gao; Han Liu; Kairong Wang; Xianxing Jiang (Chemical Engineering Journal, 2026)

Highland barley polysaccharides promoted lactose intestinal fermentation in vitro: Unveiling the dynamic response of gut microbiota and polysaccharide structure - Jingyi Wang; Jiaxin Wei; Yuxuan Fu; Qinfei Wan; Jiayi Zhou; Kai Hu; Zisheng Han (Food Research International, 2026)

Cryoprotective effect of trehalose on wheat glutenin: Structural, rheological, and molecular insights - Dan Zhang; Xiao-Shan Chen; Wen-Hui Zhang; Zi-Hao Lu; Han Tao; Wan-Hao Cai (Food Hydrocolloids, 2026)

CMOS-compatible Eu2+-doped CsCu2I3 films with improved quantum yield for white-light emission and information encryption - Daoping Peng; Lichun Zhang; Xiaoxuan Li; Xiao Zhang; Yu Fang; Chenxi Han; Ziyan Wan; Xiaohua Cheng; Guanying Xie; Zhongqiang Wang; Congcong Liu; Mengmeng Jiao; et al. (Chemical Engineering Journal, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Beyond Acute Kidney Injury : Direct Pathways Implicate Inflammatory Mechanisms in Serum NGAL’s Mortality Effect in Acute Brain Injury - Hyung Seok Guk; Yong Soo Kim; Dong-Wan Kang; Sang-Hoon Han; Museong Kim; Moon-Ku Han; Kyoungho Suk; Jae-Hong Kim; Han-Gil Jeong (Translational Stroke Research, 2026)

ALSCLIP: a symmetric encoder-decoder architecture integrating pre-trained CLIP and PointTransformer block for airborne LiDAR Scanning point cloud semantic segmentation - Xianquan Han; Jianzhou Li; Ruoming Zhai; Peng Wan; Yang Chen (International Journal of Remote Sensing, 2026)

Geometrically consistent ordinal mixture-of-experts for weight estimation of sows from multi-view point clouds - Qiang Zhai; Longhu Ma; Han Jiang; Li Wan; Yunhan Liu; Yiran Liao; Yifeng Yang; Changmeng Peng; Jinglan Lei; Yong Zhuo; Lianqiang Che; De Wu (Computers and Electronics in Agriculture, 2026)

Assessing multidimensional changes in human settlements across urban regeneration paradigms: A case study of Wuhan, China - Meng-Tian Han; Qian Cao; Hai-Yun Xu; Xiang-Wen Deng; Lun-Che Wang; Jun Wan (Sustainable Cities and Society, 2026)

Evaluation of subchronic toxicity, genotoxicity, and blood kinetics of 1,2-benzisothiazolin-3-one following oral administration - So-Young An; Soyeon Jeon; ChulBeom Park; Seol-Hee Moon; Seung-Hwa Kim; Hyo-Jin Ahn; Hyun Kim; Jong-Sam Park; Beom Seok Han; Wan-Seob Cho (Regulatory Toxicology and Pharmacology, 2026)

Anthropogenic or climate-driven? Mechanisms of the AD 1642 extreme flood Disaster of the Yellow River in Ancient Kaifeng, China - Junjie Shen; Aishan Han; Panpan Chen; Junwei Wan; Mengdie Zhao; Mingming Jia; Yan Tian; Peng Zhang; Huayong Li; Qianyu Tang; Peng Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Compact urban development and green space accessibility: Micro-evidence from Chinese cities - Shuaishuai Han; Wan Li; Mei-Po Kwan; Bindong Sun; Qianqian Liu (Land Use Policy, 2026)

Mechanistic Insights into Mercury Tolerance and Detoxification in the Potential Hyperaccumulator Fern Pteris vittata - Hongye Wan; Xiaoli Qian; Guangle Qiu; Ming Ao; Le Wang; Longchao Liang; Jialiang Han; Md. Habibullah-Al-Mamun; Jinjuan Li; Pan Wu; Shouyang He; Xiaohang Xu (Journal of Hazardous Materials, 2026)

Feasibility-enhanced and cluster-guided optimization for coordinated hydro-wind-photovoltaic dispatch under cross-regional power delivery - Zixuan Liu; Yuliang Han; Songyan Hu; Wan Liu; Wenjing Xiao; Xutong Sun; Qin Shen; Li Mo (Journal of Cleaner Production, 2026)

Wave-adaptive floating platform for hybrid triboelectric-electromagnetic energy harvesting toward marine IoT systems - Shilin Wu; Lingyu Wan; Erming Su; Gaojian Wei; Wei Tang; Siyan Pan; Jiaqi Han; Zhong Lin Wang; Leo N.Y. Cao (Chemical Engineering Journal, 2026)

Tumor-targeted dual-modality probe for preoperative MRI detection and intraoperative fluorescence guidance - Yuxin Wan; Jiaying Shi; Yucheng Fei; Fangzhu Huang; Zixin Lu; Khan Liaqat; Cuiping Han; Tonghui Huang (Chemical Engineering Journal, 2026)

Parameter Optimization of Coal Seam Hydraulic Seepage Enhancement Measures Based on Principal Component Analysis - Xuelong Li; Ruihao Han; Shumin Liu; Baolin Li; Ni Wan (Rock Mechanics and Rock Engineering, 2026)

THBS2: the key hub linking breast cancer stroma, immunity, and therapeutic response - Xi Wan; Xinchen Zhao; Yao Lin; Shujie Yang; Han Dai; Yi Li; Xiaoshan Wang (Clinical & Experimental Metastasis, 2026)

Primary amine-functionalized HTO/CMC/PVA composite films: Highly selective lithium adsorption and applications in complex lithium-containing systems - Shengkai Liu; Ruimeng Liu; Wenxuan Wang; Dandan Hu; Yu Han; Cong Li; Huiling Li; Chang Wan; Tai Peng; Wei Wang; Daxin Liang (Process Safety and Environmental Protection, 2026)

Nitrogen in light-industrial biowastes: From functional characterization to thermochemical regulation strategies - Chi Xu; Boyu Han; Shihao Meng; Ayipaiyili Yuetikuer; Hao Zhan; Xingbang Wan; Fangfang Zhu; Lijian Leng; Zhiyong Zeng; Hailong Li (Journal of Cleaner Production, 2026)

Assessing additive interactions of heat wave, fine particulate matter, and ozone on cardiovascular mortality in a typical cold region of China: A time-stratified case-crossover study - Jinghao Wan; Mingzhao She; Hanhan Wang; Lixin Zheng; Xinyue Yu; Yuqian Song; Zhongran Wang; Min Li; Xu Han; Haibo Zhou; Zhifeng Xing; Xiao Bai; et al. (International Journal of Hygiene and Environmental Health, 2026)

Tibetan kefir grain fermentation remodels the water buffalo milk metabolome and enhances antioxidant and anti-inflammatory bioactivity in vitro - Jianmei Han; Ben Li; Yuting Wang; Chen Ding; Yafan Wan (Food Research International, 2026)

Noble-metal-free high-entropy alloy aerogels with peroxidase-like activity mediated bioenzyme-free colorimetric sensor for portable and rapid detection of glyphosate - Wen Qing Jia; Jian Bing Li; Jiang Zhu; Qiao Wan; Zhen Chen; Lei Han (Food Chemistry, 2026)

A thermodynamic constraint for parameter reduction in reacting flows: Theory and experimental validation in methane-air flames - Xinlu Han; Kaidi Wan; Dingkun Yuan; Zhongqian Ling (Chemical Engineering Journal, 2026)

A spatiotemporally separated recognition–amplification strategy based on an M13 phage biological lever for immunodetection of bacteria - Chenlu Zhang; Fumei Cheng; Juanjuan Mou; Xiangyang Xiao; Xiaole Han; Li Zhang; Li Wang; Guoming Xie; Yushun Wan; Yujun Yang (Chemical Engineering Journal, 2026)

Higher nutrient availability fosters intricate bacterial networks in rhizosphere of invasive plants - Mengxin Zhao; Han Zhang; Qiao Li; Die Zhang; Jianying Guo; Rui Wang; Fengjuan Zhang; Fanghao Wan; Wanxue Liu (Applied Soil Ecology, 2026)

Multi-residue analytical method of 215 pesticides in peanut by GC-Q-Orbitrap MS/MS - Xiaofan Qi; Sufang Fan; Lijun Han; Zhijuan Meng; Xiaoying Wan; Wenbo Zeng; Canping Pan (Analytica Chimica Acta, 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

A novel hybrid physics-data driven encoder-decoder model for wind turbine wake predictions - Maokun Ye; Hanqiao Han; Minqiu Liu; Decheng Wan; Moustafa Abdel-Maksoud (Ocean Engineering, 2026)

AI-driven monitoring strategy optimization for nutrient-polluted groundwater in a desert site in Northwest China - Yuting Yan; Yu Liu; Baocai Tong; Jinsheng Wang; Rui Zuo; Yuyu Wan; Yuanzheng Zhai; Xu Han (Journal of Hydrology, 2026)

Waste cooking oil biodiesel alters combustion pathways to enhance volatile organic compound emissions and reduce intermediate/semi -volatile organic compounds in agricultural machinery - Fan Zhang; Bo Huang; Junfeng Cui; Yi Wang; Xinyi Wan; Lele Han; Gehui Wang; Yong Han; Yu Wang; Hai Guo; Min Cui (Journal of Hazardous Materials, 2026)

Evolutionary history shapes soil pH following forestation at global scales: A meta- analysis - Liankang Yang; Panmei Jiang; Qing Han; Zhuangzhuang Qian; Fangfang Wan; Hua Liu; Qiangxin Ou; Shuang Hao; Xingzhao Huang (Forest Ecology and Management, 2026)

Resource-efficient numerical computing and elastic wave behavior analysis in complex poroelastic media - Zhitao Zhang; Yuhang Guo; Zhuwen Wang; Baozhi Pan; Yibo Wang; Lin Gan; Wubing Wan; Zhaoqi Sun; Wenqiang Wang; Ruiyi Han; Jiaxu Guo; Yitong Cui (Computers and Geotechnics, 2026)

Synergizing macroscopic lateral anchoring with microscopic pore topology: A dual-optimization strategy for large bone defect reconstruction - Hao Chen; Xingzhen Li; Wenbo Yang; Yu Sun; Jinbo Zhang; Aobo Zhang; Meng Xu; Qian Wan; Xingchen Guo; Qing Han; Luquan Ren; Jincheng Wang (Chemical Engineering Journal, 2026)

Multi-dimensional analysis revealing the mechanism of T-2 toxin driving liver fibrosis: integration of network toxicology, machine learning, experimental verification, and molecular docking - Lichun Qiao; Shaoteng Shi; Liangjia Wang; Muhammad Aftab Shafiq; Jing Tang; Miaoqian Li; Ping Wan; Jingxuan Zhou; Xulei Dai; Jing Han; Yijie Guo (Chemico-Biological Interactions, 2026)

Multi-omics study to elucidate molecular mechanism of polyhexamethylene guanidine phosphate (PHMG-p)-induced pulmonary damage in mice - Jung Dae Lee; Hyang Yeon Kim; Jueng-Eun Im; Handule Lee; Juyoung Park; Kwangsik Park; Keunsoo Kang; Hye Gwang Jeong; Sehyun Chae; Daehee Hwang; Beom Seok Han; Wan-Seob Cho; et al. (Archives of Toxicology, 2026)

Influence of soil types defined by soil genesis on the qualitative and quantitative detection of microplastics in soil by mid-infrared spectroscopy - Linwei Cai; Chunxu Wan; Zengling Yang; Zhuolin Shi; Xintong Zhang; Jinzhao Li; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Structure–function relationships in chitosan films containing ZIF-8-confined Ligusticum jeholense essential oil: pH-triggered release and apple ring rot control - Xiao-Yi Tong; Yun-Feng Liu; Zhi-Hong Xu; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An; Fei Cao (Food Chemistry, 2026)

A highly reproducible multimode fiber sensor via synergistic optimization of biobased reinforcement and conductive network - Wang Shanping; Wan Haicheng; Guo Pengshuai; Han Wenqi; Liu Zengtian; Gaoqi Wang (Chemical Engineering Journal, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Diversity of arbuscular mycorrhizal fungi of Taiwan cypress along altitude in tropical forests - Wan-Rou Lin; Hsuan-Min Cheng; Ren-Cheng Liu; Tzu-Chao Lin; Lei-Chen Lin; Pi-Han Wang (Tropical Ecology, 2026)

Mechanistic insights into the neuroprotective effects of yangyin formula on cerebral ischemia-reperfusion injury via the IL-17A/MAPK/NF-κB signaling pathway - Kun Shi; Haofang Wan; Jin Han; Jiehong Yang; Haitong Wan (Journal of Molecular Histology, 2026)

Weakening sensitivity of China’s terrestrial evapotranspiration to vegetation greening in a warmer world - Hui Guo; Nan Wei; Zhuoyi Tu; Huiping Huang; Fang Wan; Han Wang; Yanmei Wang; Shengzhi Huang (Agricultural and Forest Meteorology, 2026)

FTCSEM—A FORTRAN-based parallelized 1D CSEM forward and inversion program for arbitrary source-receiver geometry - Wei-ying Chen; Si-xu Han; Wan-ting Song; Yu-lian Zhu; Zheng Liu (Applied Geophysics, 2026)

An Adaptive Visual–Tactile Fusion Reinforcement Learning Method for Underwater Manipulator Grasping - Duo Wan; Wei Chen; Yongqing Shi; Lu Han (Journal of Marine Science and Engineering, 2026)
Underwater manipulator grasping remains challenging because image blur, light attenuation, and flow-induced disturbances degrade perception and control. These factors make target localization, contact judgment, and stable lifting difficult, especially when visual degradation and tactile fluctuation occur together. We propose AVT-TD3, an adaptive visual–tactile fusion reinforcement learning method for underwater manipulator grasping. AVT-TD3 constructs a unified policy state from visual observations, short-horizon tactile variations, and manipulator proprioception. A gated fusion module adjusts the contribution of each sensory branch, while an action modulation mechanism limits abrupt velocity-command changes during contact establishment and lifting. We train the continuous grasping policy with Twin Delayed Deep Deterministic Policy Gradient (TD3) and evaluate it in simulation under different turbidity, flow velocity, and target conditions, followed by controlled water-tank feasibility validation. Simulation results show that AVT-TD3 achieves better performance than Deep Deterministic Policy Gradient (DDPG), Soft Actor-Critic (SAC), and standard TD3 in success rate, completion steps, slip rate, and velocity-command smoothness. In the standard test scenario, AVT-TD3 achieves a success rate of 92.7%, an average of 76 completion steps, a slip rate of 4.1%, and an action variation magnitude of 0.20. Controlled water-tank tests further support the feasibility of deploying AVT-TD3, although open-water validation remains for future work.

Dynamic dose–time proteomic profiling of cadmium exposure in rat prefrontal cortex - Zhijian Hu; Feng Han; Hao Gao; Sheng Wan; Hui Liu; Li Jie; Yinghui Yin; Maoqin Tian; Yong Yang; Wenjie Chen; Xiao Tan; Xinxin Shi; et al. (NeuroToxicology, 2026)

Crystallization regulation for al and Fe impurity migration and removal from waste quartz crucible with combined process of High-Temperature Roasting-Acid leaching - Suoque Wu; Shifeng Han; Xiaohan Wan; Ning Tan; Shicong Yang; Kuixian Wei; Wenhui Ma (Minerals Engineering, 2026)

Speciated full-volatility organic compound emissions from typical agriculture machinery in China - Yi Wang; Lele Han; Bo Huang; Xia Xu; Xinyi Wan; Yubao Chen; Yong Han; Min Cui; Yu Wang; Hai Guo; Fan Zhang; Gehui Wang (Journal of Environmental Sciences, 2026)

Mechanism and geological significance of methane adsorption and desorption in deep dry and wet high-rank coal under supercritical conditions - Jie Huang; Shuangbiao Han; Yu Qiao; Yongping Wan; Zhenchuan Wang; Hongtao Gao; Liang Qiao; Yurun Rui (Fuel, 2026)

Structural characterization and anti-aging mechanism of Codonopsis pilosula polysaccharides - Meiqi Wan; Rong Han; Xiaoai Bao; Yizheng Sun; Hailong Xu; Yanlin Wang; Aihong Zhao; Youbo Zhang (Food Research International, 2026)

Saponins: advanced extraction, quantification techniques, multi-target bioactivities, and applications in food and health - Qiao-Yu You; Yue-Han Qi; Jia Wu; Liang Zou; Zi-Peng Wang; Yan Wan; Jing-Wei Huang (Food Chemistry, 2026)

The impact of radiative cooling paint on a factory building in tropics - Di Han; Yongping Long; Man Pun Wan; Bing Feng Ng (Building and Environment, 2026)

Gap-filled spatiotemporal reconstruction of XCH4 data and analysis of methane emission patterns - Qian Xiao; Yong Wan; Ge Han; Yu Liu; Yuhang Liu; Xiaowen Li; Hongyu Zhou (Atmospheric Pollution Research, 2026)

Smad7 drives cisplatin resistance in ovarian cancer via a PRMT5-dependent mechanism - Jinlong Ji; Kexin Wang; Geshuyi Chen; Manman Zhao; Cong Wan; Yun Han; Yanli Zheng (Tissue and Cell, 2026)

Enhancing urban ecological connectivity through small stepping stones: A solution for inequitable geographical distribution of blue-green spaces (IGDBGS) - Yiwen Han; Yijing Ren; Min Wan; Mingxuan Wan (Journal of Environmental Management, 2026)

Enhancing the efficiency of catalytic transfer hydrogenation in the production of γ-valerolactone from biomass with metal-organic frameworks supported by ruthenium-substituted phosphovanadomolybdic acid - He Wan; Fanqi Yan; Yue Zhao; Yongwei Han; Zhong Sun; Xixin Duan (Journal of Environmental Chemical Engineering, 2026)

Instant steam-priming as a novel pre-brewing strategy: Unraveling the metabolomic basis for modulating taste attributes across six tea categories - Yuan-Yuan Ma; Ying Gao; Nan Han; Kai Zhao; Julieta Domínguez-Soberanes; Jorge A. Zegbe; Fang Wang; Jian-Xin Chen; Wan-Ping Fang; Yong-Quan Xu (Food Research International, 2026)

Cryoprotective effect of water extractable arabinoxylan on different molecular weights of wheat glutenins - Han Tao; Ya-Ni Li; Hai-Yuan Zhou; Shan Li; Wan-Hao Cai; Hui-Li Wang; Dong-Lin Su (Food Hydrocolloids, 2026)

Soil amendments improved physiological characteristics, grain yield, and water use efficiency of common buckwheat under multi-year continuous cropping - Qi Wang; Xiaoyi Han; Qixuan Wang; Minlong Du; Xinyue Lei; Jiahao Ge; Rong Zhong; Chenxi Wan; Xiaoli Gao; Pu Yang; Jinfeng Gao (European Journal of Agronomy, 2026)

Unraveling -Ni2+/-Mn2+ doped Ti3CNTx MXene nanowebs for high-performance asymmetric supercapacitors - Sabeen Fatima; Yu Sun; Lei Han; Nan Han; Muyang Li; Safia Khan; Klaus Leifer; Xiaoqing Jiang; Jie Li; Qingsong Wan; Hongji Fang; Yafei Ning; et al. (Chemical Engineering Journal, 2026)

Antifungal Susceptibility and Multilocus Sequence Typing of Pichia kudriavzevii (Candida krusei) from a Tertiary Hospital in Shanghai - Guo Chen; Li Li; Junhao Zhu; Yixin Huang; Jieyi Wan; Demin Han; Min Zhu (Mycopathologia, 2026)

Integrating eDNA metabarcoding and functional trait analysis to uncover fish community structure and assembly mechanism in the Taiwan strait - Weiyi He; Hao Huang; Lei Wang; Danyun Ou; Jiaqiao Wang; Runze Han; Yanxu Zhang; Jinli Qiu; Weiwen Li; Kar-Hoe Loh; Sze-Wan Poong (Frontiers in Marine Science, 2026)
Marine fish communities in coastal systems are increasingly shaped by environmental gradients associated with anthropogenic pressures and climate variability, yet how these factors influence community assembly and functional traits remain poorly understood. In this study, environmental DNA (eDNA) metabarcoding using the 12S MiFish primer with 33 water samples was integrated with taxonomic and functional diversity analyses, co-occurrence network analysis, the neutral community model, hierarchical modeling of species communities, and single-trait-based community-weighted means to investigate fish communities in the Taiwan Strait (TWS). This interdisciplinary approach provides both a unique perspective and a comprehensive framework for fish biodiversity assessment. Fish communities exhibited high modularity and weak interspecific interactions, with an uneven distribution of species within functional space, indicating elevated ecological vulnerability. Community assembly was jointly governed by stochastic and deterministic processes, with NO₂⁻ identified as a significant environmental driver shaping fish community assembly. Notably, fish communities in the inshore and principal axis regions exhibited higher clustering coefficient but lower network modularity compared to other regions. Hierarchical modeling of species communities and community-weighted means further indicated clear distributional and trait differences among fish from the estuarine to offshore areas, consistent with species-specific responses to environmental gradients from inshore to offshore areas. Overall, TWS fish communities are dominated by species with very small and small body-length traits, while reef-associated fishes are mainly concentrated in inshore and midshore regions. Fish community assembly and functional traits in TWS exhibited systematic variation along the offshore distance gradient and were jointly modulated by key environmental factors.

Quantitative analysis and toxicological mechanisms of various male infertility inducers: A network meta-analysis and pharmacological approach - Muhammad Arif Asghar; Ao Zhang; Shixin Tang; Hang Han; Bing Wan; Jingwei Wu; Li Ping Wong; Xiao Zhang; Qinjian Zhao (Reproductive Toxicology, 2026)

How precipitation extremes respond to rapid warming over the Tibetan Plateau - Shuping Li; Dongdong Wang; Zhengyi Han; Zhe Yin; Shiquan Wan; Pengcheng Yan (Journal of Hydrology, 2026)

Synergistic microbicidal effects of plasma-activated sodium hypochlorite on fresh produce surfaces - Jae-Wan Ryu; Jin-Young Han; Soo-Hwan Kim; Dong-Hyun Kang (Innovative Food Science & Emerging Technologies, 2026)

Unveiling the binding mechanism between egg white proteins and wheat glutens during the dough mixing process - Dan Zhang; Peichuang Li; Shan Li; Haiyuan Zhou; Han Tao; Wan-Hao Cai (Food Hydrocolloids, 2026)

Crop rotations reshape the fate of residual and current fertilizer nitrogen: A consecutive 15N tracing study in flax-based systems on the Loess Plateau - Haidi Wang; Xingkang Ma; Bin Yan; Yuhong Gao; Zhengjun Cui; Bing Wu; Yifan Wang; Jing Han; Mingli Wan (Field Crops Research, 2026)

Multi-strategy rehabilitation enhances nitrogen removal in a one-stage partial nitritation/anammox reactor - Xinyu Wan; Zhicheng Zhao; Yunpeng Zhao; Wan Sun; Shilong Liu; Xiangyu Han; Xi Lu; Yasong Chen; Weiwei Cai (Environmental Research, 2026)

Divalent cations synergistic doped V-based cathode towards high-performance aqueous zinc-ion batteries - Qiuyi Wu; Cuixian Hu; Jinrong Le; Yuhong Chen; Xiao Yang; Liangwei Liu; Yi Xiao; Houzhao Wan; Zhou Yang; Xiang Ding; Lili Han (Chemical Engineering Journal, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

Quantitative study on the local structure and macroscopic property correlations in binary lithium germanate melts - Yufan Zhao; Han Sun; Jinglin You; Jiawen Lu; Jian Yang; Jiansheng Geng; Xiang Xia; Guopeng Liu; Kai Tang; Liming Lu; Qingli Zhang; Songming Wan (Chemical Engineering Journal, 2026)

Nitrogen dilemma in Chinese crop-livestock systems: Assessing mitigation potential and exploring optimization pathways from the perspectives of utilization efficiency and pollution hotspots - Zhijian Wu; Han Liang; Zhong Liu; Haijiao Du; Liujie He; Zeyang Xie; Jinqi Zhu; Bofu Zheng; Wei Wan (Agricultural Systems, 2026)

Anti-melanogenesis and Anti-wrinkle Effects of Novel Peptides Derived from Tenebrio Molitor L. (mealworm) Expressed by Gamma-Irradiation - Hanui Lee; Gyeong Han Jeong; Ji Wan Choi; Tae Hoon Kim; Byung Yeoup Chung; Seung Sik Lee (International Journal of Peptide Research and Therapeutics, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Subchronic oral toxicity and genotoxicity of Aurantii Fructus Immaturus water extract - So-Young An; Si-Whan Song; Hyun-Suk Heo; Chang-Wok Park; Min-Sub Kim; Woo-Joo Lee; Yoo-Jin Park; Jae-Ho Shin; Beom Seok Han; Wan-Seob Cho (Regulatory Toxicology and Pharmacology, 2026)

South China in the Rodinia-Gondwana transition: Constrains from the Ediacaran Doushantuo Formation of the north Yangtze Block - Lisha Hu; Jie Yang; Yuansheng Du; Zuozhen Han; Hongwei Kuang; Yongqing Liu; Chao Han; Yi Zhang; Wei Jin; Le Wan (Precambrian Research, 2026)

Transcription factor NlHsf regulates NlABCG7 overexpression in the sulfoxaflor resistance of Nilaparvata lugens - Zhao Li; Qing Han; Kaixin Gu; Xianyan Su; Shun He; Hu Wan; Jianhong Li; Xuexiang Ren (Pesticide Biochemistry and Physiology, 2026)

Bio-inspired rigid-Soft interaction for robust picking underwater - Shuqiao Zhong; Wanghongjie Qiu; Xudong Han; Chaoyang Song; Zhiyuan Zhou; Fang Wan; Jian Lin (Ocean Engineering, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Optimization strategies for cultural landscape recreational safety patterns to mitigate urban heat risks - Y. Mao; H. Han; X. Meng; Y. Wan (International Journal of Environmental Science and Technology, 2026)

Lemon Defect Detection Based on Seagull Algorithm Optimization–Support Vector Machine Model - Hongqiang Wan; Yibo Wan; Zechen Yang; Yuanyuan Han; Wanxin Wu; Minru Yao (Applied Fruit Science, 2026)

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Iridoid glycosides and phenolic glycosides from Gentiana rhodantha and their anti-inflammatory activities - Han-Fei Liu; Wan-Jun Pu; Ting Zhao; Xiao-Die Shu; Jun-Jie Lan; Chao Chen; Wei-Dong Pan; Ni Zhang; Jin-Yu Li (Phytochemistry, 2026)

Effects of electrode geometry on the physicochemical properties and antimicrobial efficacy of plasma-activated water generated by surface dielectric barrier discharge - Jae-Wan Ryu; Jin-Young Han; Sangheum Eom; Soo-Hwan Kim; Dong-Hyun Kang (International Journal of Food Microbiology, 2026)

High-resolution marine records of human-nature interactions in the Yellow River Basin since 2.2 kyr ago - Wenqiang Pei; Shiming Wan; Peter D. Clift; Jin Zhang; J. Paul Liu; Yongming Han; Debo Zhao; Zhendong Luan; Zhaojie Yu; Zehua Song; Anchun Li (Global and Planetary Change, 2026)

N2O and NO formation influenced by metal elements during coal pyrolysis and char combustion - Yanjun Zuo; Zhaoxin Wan; Haiyang Li; Ping Liu; Xiaoshuo Liu; Yingchuan Zhou; Zhi Han; Yufeng Duan (Fuel, 2026)

X-type shear connector in steel-ECC composite structures: Shear behavior and analytical model - Menghan Hu; Youhui Ruan; Jiangquan Wan; Yulong Ni; Xianzhuo Jia; Pandao Li; Qiang Han (Engineering Structures, 2026)

Turning on Mn2+ luminescence through linear defect clusters: Harvesting mechanoluminescence and multimodal emission - Jinyi Zhang; Mengmeng Cao; Congcong Han; Mengyuan Li; Jieqiong Wan (Chemical Engineering Journal, 2026)

Shifts in epidemic patterns and age dynamics of RSV, IFV, and SARS-CoV-2 in Chinese children following COVID-19 non-pharmaceutical intervention relaxation, 2017 − 2024 - Yiguo Zhou; Jian-Bo Xia; Meimei Luo; Wan-Xue Zhang; Shan-Shan Zhang; Le Ao; Han Yang; Qin-Yi Ma; Juan Du; Yu-Ting Wang; Ninghua Huang; Xing-Wen Hu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Phase-regulated colloidal FeS for controlled sulfidation and precise copper–arsenic separation under strongly acidic conditions - Xingfei Zhang; Wei Sun; Haisheng Han; Xianzhong Bu; Sen Wang; Xuewen Song; Chenglong Lu; Jiwei Xue; He Wan; Chonghui Zhang (Process Safety and Environmental Protection, 2025)

Mechanical behavior of surface conductors induced by drill string vibrations during deepwater drilling - Qishuai Yin; Jingxuan Tang; Zengcheng Han; Yao Zhou; Hongyu Wan; Yongqi Ma (Ocean Engineering, 2025)

Parametric analysis of bubble wake characteristics of underwater vehicle - Yang Han; Wan-yu Zhao; Jue-yu Dong; Ruo-xin Li; Yan-yuan Wu; Yong-hao Wang (Ocean Engineering, 2025)

Pelletization and steam reactivation of steel slag-derived calcium-based sorbent for CO2 capture - Nai Rong; Yuhan Wang; Zhihang Guo; Kaiwei Liu; Xiuliang Shi; Long Han; Lichao Ge; Geng Wang; Chao Hu; Xiaokang Wan (Journal of Environmental Chemical Engineering, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Unique ectomycorrhizal fungal association is a major conservation dilemma for the threatened ectomycorrhizal tree species - Ren-Cheng Liu; Wan-Rou Lin; Alija Bajro Mujic; Pi-Han Wang (Journal for Nature Conservation, 2025)

Removal of starch granule-associated lipids from normal and waxy wheat starches: Effects on properties, retrogradation, digestion, and molecular mechanisms - Han Tao; Hai-Yuan Zhou; Shan Li; Ya-Ni Li; Wan-Hao Cai; Hui-Li Wang (Food Chemistry, 2025)

Stereoselectivity during enzymatic oxidation of catechins and their products' characteristic in taste receptors and color properties - Zekai Wang; Qing-Qing Cao; Mingchun Wen; Yahui Li; Yuqing Cui; Zisheng Han; Xiaochun Wan; Chi-Tang Ho; Yong-Quan Xu; Liang Zhang (Food Chemistry, 2025)

Tartary buckwheat-soy protein isolate composite gels: gelling, rheological, water-retention, and texture characteristics at different ratios - Xiao Han; Gen Ma; Lin Wang; Ting Cheng; Yangyang Guo; Liangzhen Jiang; Yan Wan; Xiaoqin Zheng; Changying Liu; Lianxin Peng; Gang Zhao; Xiulan Guo; et al. (Food Hydrocolloids, 2025)

Retraction notice to ‘Ancient forest plants possess cytotoxic properties causing liver cancer HepG2 cell apoptosis’ [Environ. Res. 241 (2024) 117474] - Xiaochen Yue; Nyuk Ling Ma; Jiateng Zhong; Han Yang; Huiling Chen; Yafeng Yang; Su Shiung Lam; Lijun Yan; Bjarne Styrishave; Tomasz Maciej Ciesielski; Wan-Xi Peng; Christian Sonne (Environmental Research, 2025)

Quercetin-loaded milk-derived extracellular vesicles for the treatment of inflammatory bowel disease by alleviating senescence-associated cell cycle arrest - Runrun Wan; Tingting Cao; Meng Deng; Chengbiao Hu; Caixiao Liu; Yijuan Han; Na Zhao; Qiaoning Wang; Xueru Li; Xiangdong Wang; Chenghu Hu; Zhang Yuan (Chemical Engineering Journal, 2025)

Comparative study of the stability of composite cathodes based on sulfide solid electrolytes for all-solid-state lithium-ion batteries - Jae-Ho Park; Jiwon Jeong; Daseul Han; Jun Tae Kim; Hun-Gi Jung; Woo Young Yoon; Kyung-Wan Nam; Kyung Yoon Chung (Chemical Engineering Journal, 2025)

Green synthesis of bioinspired superhydrophilic copolymers from functionalized lactic acid and maltotetraose for sustainable applications - Yiyang Kang; Yan Jiao; Han Song; Yinuo Wan; Hao Ning; Lixia Bao; Weibo Kong; Jiliang Wang (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Integrated Physiological and Transcriptomic Analysis Reveals the Drought Stress Response Mechanisms in Chrysanthemum morifolium (Ramat.) Tzvel. ‘Boju’ - Tao Wang; Qian Shao; Min-yan Xu; Cheng Zhao; Lu Liu; Wen-tin Jiang; Qian-kun Han; Wan-yi Wang (Plant Molecular Biology Reporter, 2025)

Hippocampal Extracellular Matrix Protein Laminin β1 Regulates Neuropathic Pain and Pain-Related Cognitive Impairment - Ying-Chun Li; Pei-Yang Liu; Hai-Tao Li; Shuai Wang; Yun-Xin Shi; Zhen-Zhen Li; Wen-Guang Chu; Xia Li; Wan-Neng Liu; Xing-Xing Zheng; Fei Wang; Wen-Juan Han; et al. (Neuroscience Bulletin, 2025)

Genetic Variation A118G in the OPRM1 Gene Underlies the Dimorphic Response to Epidural Opioid-Induced Itch - Xiaomeng Zhou; Ai-Lun Li; Wan-Jie Du; Pengyu Gao; Bin Lai; Fang Fang; Qingjian Han; Jing Cang (Neuroscience Bulletin, 2025)

Genetic association between SKA2 rs7208505 and preterm birth in Korean women - Eun Jo Lee; Sung Ho Han; Yun Dan Kang; Jong Soo Kim; Jin Wan Park; Han Jun Jin (Molecular Biology Reports, 2025)

Zircon U-Pb Ages and Sr-Nd-Hf Isotopes Geochemistry of I-Type Granites in the Jiangda-Weixi Region, Eastern Tibet: Implications for the Tectonic Evolution of the Paleo-Tethyan Orogen - Rui Gao; Tao Wu; Andrew C. Kerr; Han Liu; Long Xiao; Wan Huang (Journal of Earth Science, 2025)

Retraction Note: long non-coding RNA H19X promotes tumorigenesis and metastasis of colorectal cancer through regulating the miR-503-5p/KANK1 axis - Zihan Yuan; Haizhou Zhao; Qiaoming Zhi; Sentai Wang; Chao Liu; Ye Han; Zhihua Xu; Fei Liu; Xingyi Liu; Xinquan Zan; Qiang Wang; Daiwei Wan Genes (Genes & Genomics, 2025)

Towards COP29 climate equity: Multi-scale trade-driven inequality in China’s land-use carbon emissions - Shan Guo; Weiyi Xia; Yaohua Wan; Xiaofang Wu; Wenjing Han; Hossein Azadi (Land Use Policy, 2025)

Preparation and characterization of PAPP@MF microcapsules for enhancing the safety of PVDF - Long-Tai Qi; Lei Ma; Zhi-Xiang Xing; Ye-Cheng Liu; Wan-Zheng Lu; Han Han; Tian-Yu Zhou; Yao Wu (Journal of Fluorine Chemistry, 2025)

Enhancement of syngas production via plastic gasification in low-concentration CO2 by using spent lithium-ion batteries-derived black mass - Dong-Wan Cho; Hyeop-Jo Han; Jae-Hoon Hwang; Yongtae Ahn; Hyeonjung Yu (Journal of Environmental Management, 2025)

A systematic survey and meta-analysis of the segment anything model in remote sensing image processing: Challenges, advances, applications, and opportunities - Zhipeng Wan; Sheng Wang; Wei Han; Yuewei Wang; Xiaohui Huang; Xiaohan Zhang; Xiaodao Chen; Yunliang Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Organophosphate esters in surface water across China: Occurrence, distribution, driving factors and ecological risk - Zhenfei Han; Jinze He; Guangshuo Chai; Xizhe Wan; Tianqi Jiang; Xiaomei Cui; Yindong Tong; Xiaoyu Cui; Hongyang Cui (Environmental Research, 2025)

Revealing the role of Fe particle size in soft magnetic geopolymer for enhancing energy conversion in airport pavement induction heating - Gonghui Gu; Xinchi Xu; Jinsheng Han; Lin Wan-Wendner; Zhiji Gao; Rongze Fu; Chuanqing Fu; Tao Ma (Energy and Buildings, 2025)

Amino acid-induced supramolecular assembly defective carbon nitride for efficient photocatalytic CO2 reduction - Rui Li; Liting Lai; Si Li; Shipeng Wan; Wenbei Jia; Yu Han; Ruixuan Chu; Qin Zhong; Zhaoxiang Zhong (Chemical Engineering Journal, 2025)

Crystal refinement in biaxially stretched capacitor films for enhanced energy storage - Qi Wu; Zhicheng Li; Gang Chen; Shuai Zhang; Wenyan Wang; Weicai Wan; Rui Han; Min Nie (Chemical Engineering Journal, 2025)

Unveiling molecular transformations and mechanisms of soil organic matter during thermal remediation across temperatures - Han Gao; Shang Gao; Lei Wang; Zhen Song; Xiaolei Qu; Minli Wang; Tao Long; Jinzhong Wan (Chemical Engineering Journal, 2025)

Fs–LA–ICP–MS U–Pb dating of fluorite and its prospect for geological application - Yan-Wen Tang; Na Liu; Jun-Jie Han; Yan Liu; Wan-Ting Ge; Jian-Feng Gao; Ting-Guang Lan (Chemical Geology, 2025)

Response mechanisms of nitrogen-cycling microbiota and metabolic functions to nitrogen input in the Panax ginseng rhizosphere - Kexin Li; Mei Han; Mingming Wan; Limin Yang (Plant and Soil, 2025)

Genome-wide identification and expression analysis of NRT2 gene family in Tartary buckwheat suggests the potential role of FtNTR2.4 in low nitrogen response - Daiying Xu; Yaoxuan Zou; Nan Hu; Han Li; Junjie Yin; Jiting Wang; Xi Wu; Dabing Xiang; Jianglin Zhao; Xiaoqin Zheng; Yan Wan; Yanxia Liu; et al. (Physiology and Molecular Biology of Plants, 2025)

Study on the characteristics of vibration acoustic signals and rupture grading for reactor pipeline leaks - Xinyu Zhao; Zhuorun Zhang; Xiangpeng Du; Yu Wang; Jinchuan Yang; Zhangjun Feng; Ruiyang Zhong; Chuang Han; Jiaxin Mo; Jinlong Wan; Zhida Yang (Annals of Nuclear Energy, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

MDS-PointPillars: A lightweight obstacle identification method in farmland based on three-dimensional LiDAR for autonomous navigation - Xianlu Guan; Huan Wan; Weikang Han; Rui Jiang; Yuanzhen Ou; Yuli Chen; Zhiyan Zhou (Computers and Electronics in Agriculture, 2025)

ET-PatchNet: A low-memory, efficient model for Multi-view Stereo with a case study on the 3D reconstruction of fruit tree branches - Hao Wan; Xilei Zeng; Zeming Fan; Qinhu Chen; Ke Zhang; Han Zhang (Computers and Electronics in Agriculture, 2025)

Kinetics and mechanism of iron leaching from scrap copper smelting slag flotation tailings by hydrochloric acid - Fei Han; Yifan Li; Xiaojie Zhuang; Mingyao Zhao; Weijie Song; Yinhua Wan (Journal of Environmental Chemical Engineering, 2025)

Heteroatom-doped, vinegar residue-derived fluorine/chlorine Co-doped vertical graphene-supported carbon quantum dots as high-efficiency all-carbon electrodes for water electrolysis hydrogen production - Han Yin; Yang An; Chunyu Li; Yu Yan; Rui Su; Chunyang Wan; Bin Jiang; Shanshan Bai; Firdoz Shaik (Journal of Environmental Chemical Engineering, 2025)

Discovery and identification of novel color compound formed from EGCG upon heating: Integrated multispectral, sensory evaluation, metabolomics, and nuclear magnetic resonance - Zongde Jiang; Zixin Zhao; Zisheng Han; Jiaping Ke; Chunyin Qin; Chi-Tang Ho; Xiaoting Zhai; Yijun Wang; Liang Zhang; Xiaochun Wan (Food Chemistry, 2025)

Insights into the structure modulation and lubrication behavior of phase change capillary oleogels during oral processing - Chuanwu Han; Gaoshang Wang; Xinyi Xia; Guangxin Feng; Shouwei Yin; Jinmei Wang; Zhili Wan; Jian Guo; Xiaoquan Yang (Food Hydrocolloids, 2025)

Electrocatalytic degradation of norfloxacin using La-Sb co-doped Ti/SnO2 electrodes - Zhi Zheng; Xiao Han; Chenliang Zhou; Jieliang Chen; Houxing Chen; Meina Guo; Huimin Xie; Weidong Xiao; Yinhua Wan; Peihai Ju; Kang Hu (Environmental Research, 2025)

The construction of high-performance asymmetric supercapacitors by Bi-MOF-derived carbon skeleton with in situ activated Bi2O3/C and B-rGO/amorphous NiCoB - Xin Sun; Shang Wu; Lihua Chen; Qiyue Tong; Lulu Han; Pengfei Wan; Yuzhi Sun; Lihong Wang; Quanlu Yang (Chemical Engineering Journal, 2025)

Simultaneous exciton control and electron recycling in pyrene-based stable blue fluorescent organic light-emitting diodes via hybridized local and charge transfer and triplet-triplet fusion mechanisms - Yi Sak Lee; Heejun Nam; You Na Song; Wan Pyo Hong; Won-Sik Han; Taekyung Kim (Chemical Engineering Journal, 2025)

An Automatic Route Planning Method for Digital Transmission Lines Based on Remote Sensing Spatial Model of Ground Obstacles and Ant Colony Algorithm - Guoping Wan; Xiping Han; Xing Zhao; Meng Liu (Journal of the Indian Society of Remote Sensing, 2025)

Endophytic Bacterium Paenibacillus illinoisensis Y11 Promotes Duckweed Growth and Enhances Cadmium Pollution Remediation - Zhi-Qun Chen; Ai-Juan Tan; Yi-Fei Wan; Yu-Han Dong; Xiao Yang; Gui-Li Yang (Current Microbiology, 2025)

Comparative study on the microstructural mechanism of thermal aging embrittlement in 17-4 PH and 15-6 PH stainless steels at 350 °C - Yupeng Yin; Ziwei Guan; Fangjie Shi; Tieqiao Zhang; Qunjia Peng; Farong Wan; Wentuo Han (Annals of Nuclear Energy, 2025)

Sex-Associated Indels and Candidate Gene Identification in Fujian Oyster (Magallana angulata) - Yi Han; Yue Ning; Ling Li; Qijuan Wan; Shuqiong Li; Ying Yao; Chaonan Tang; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Fishes, 2025)
Sex determination is a fundamental biological process governing animal reproduction. Although substantial progress has been made in elucidating its genetic basis, the genetic architecture underlying complex sex determination systems remains poorly understood. In this study, we identify sex-associated insertion–deletion (indel) variants, screen candidate genes, and compare sex-associated variation across populations with different genetic backgrounds in the Fujian oyster (Magallana angulata). Based on whole-genome resequencing data of a culture strain (designated FL), a total of 299,774 high-quality indels were identified. By integrating genome-wide association analysis (GWAS), fixation index (FST) analysis, and sex-biased genotype frequency comparisons, 77 overlapping sex-associated indels were identified, predominantly clustered within a 1.8 Mb (8.3–10.1 Mb) region on chromosome 9. Principal component analysis (PCA) based on the sex-associated markers and their subsets consistently separated male and female individuals in the FL strain. For two representative sex-associated indels, PCR-based genotyping methods were developed and validated. Functional annotation identified putative candidate genes for sex determination, including PKD1L1, 5-HTRL, SCP, and CCKRa. Comparative analysis of variants within PKD1L1 across wild, farmed, and selectively bred populations revealed a progressive enrichment of male-linked alleles in domesticated and selectively bred groups, particularly in male individuals. This study provides direct evidence that sex in the Fujian oyster is genetically determined and reveals that domestication and artificial selection may drive the emergence of major sex-determining loci, offering important insights into the genetic basis of sex determination in the Fujian oyster, and establishing a theoretical and practical foundation for molecular marker-assisted breeding of monosex lines for this species.

Refined assessment of carbon emissions from land use in China: A research framework based on “provincial accounting-efficiency assessment-spatial synergy” - Jintao Li; Yun Huang; Han Liang; Liujie He; Haijiao Du; Jinqi Zhu; Bofu Zheng; Wei Wan (Sustainable Cities and Society, 2025)

A site experiment on the effects of cool coating in a residential community under the tropical climate - Yong Ping Long; E. V. S. Kiran Kumar Donthu; Di Han; Man Di Zhou; Xiao Qin Zhang; Bing Feng Ng; Man Pun Wan (Sustainable Cities and Society, 2025)

Ninety-day repeated oral toxicity and genetic toxicity studies of powderized Aurantii Fructus Immaturus - Soyoung An; Songyeon Kim; Si-Whan Song; Hye-Seon Heo; Changwook Park; Minseob Kim; Wooju Lee; Yujin Park; Jae-Ho Shin; Beom Seok Han; Wan-Seob Cho (Regulatory Toxicology and Pharmacology, 2025)

Conversion of phenol into polymers from wastewater via nonradical peroxydisulfate activation process - Yi-Tong Lv; Xiao-Hui Wang; Jun Cao; Lu Zhang; De-Ming Zhao; Hui-Bing Shi; Wei-Meng Si; Wan-Ju Zhang; Jia Song; Xu Han (Process Safety and Environmental Protection, 2025)

Optimization of operating conditions for intermittent aera-tion of constructed wetlands for treatment of livestock wastewater Equilibrium efficiency and effects - Chuanyu Wan; KangHui Zhu; Jiayi Sun; JiYan Chen; FengPeng Han (Journal of Water Process Engineering, 2025)

Bioinspired functional surface with curved topography and dual heterogeneous wettability for enhanced fog collection - Yanling Wan; Yuhong Yin; Han Yu; Yonghua Wang; Jingze Xue (Journal of Water Process Engineering, 2025)

Revisiting the quantitative relationship between groundwater evapotranspiration and water table depth: A numerical study - Shu-Cong Tan; Xiao-Wei Jiang; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Li Wan; Yi-Jian Zeng (Journal of Hydrology, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Response of PM2.5 concentration to climate variability and climate change prediction in China - Wan Li; Hujia Zhao; Changshuang Wang; Peng Wang; Dong Han; Chengyu Wang; Wenjing Yuan; Shuanglu Bo (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Engineering cobalt coordination environment with dual heteroatom doping for boosting urea-assisted hydrogen evolution - Xueqing Pan; Jiaxiang Qiu; Siyuan Tang; Quanjiang Lv; Jianling Dong; Nan Jiang; Luyu Liu; Yangyang Wan; Xinchun Yang; Jian Han; Fuzhan Song (Fuel, 2025)

Diaporthein B/ZnO/chitosan biodegradable film for postharvest preservation of apples: Characterization and application - Hui-Fang Du; Fei Cao; Zhi-Hong Xu; Ya-Xian Gao; Ya-Hui Zhang; Sen Pang; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An (Food Packaging and Shelf Life, 2025)

Ultra-stretchable and subzero-healable epidermal electrodes enabled by kirigami-networked microcrack engineering for human-machine interactions - Ying Xiao; Yilu Cui; Jie Wan; Yang Yang; Xiangrong Shi; Lingui Han; Ziming Wang; Dianpeng Qi; Bo Jiang; Kuiyuan Zhang (Chemical Engineering Journal, 2025)

Data-driven machine learning with SHAP for predicting multiple biochar properties from agricultural and forestry waste - Kun Xiang; Hualin Chen; Chuanqing Yao; Yuanyuan Wan; Han Ren; Jiangmin Zhou (Biomass and Bioenergy, 2025)

Chlorophyll deficient 5 encodes a DNA helicase and is essential for chloroplast development in rice - Weichi Liu; Xiaonan Han; Jiaxin Wei; Jie Yang; Yingchun Wan; Hongxia Yang; Yao Deng; Nan Wang; Ping Feng; Wenqiang Shen (Theoretical and Applied Genetics, 2025)

Effects of fertilizers on arsenic accumulation in ratoon rice: implications for human health risks - Kai-Wei Juang; Han-Ting Hsu; Wan-Ting Chiao; Chien-Hui Syu; Bo-Ching Chen (Environmental Geochemistry and Health, 2025)

Data-driven differentiable model for dynamic prediction and control in wastewater treatment - Yun-Peng Song; Wen-Zhe Wang; Yu-Qi Wang; Wan-Xin Yin; Jia-Ji Chen; Hao-Ran Xu; Hao-Yi Cheng; Fang Ma; Han-Tao Wang; Ai-Jie Wang; Hong-Cheng Wang (Water Research, 2025)

Top-of-atmosphere radiometric reference model for stable land sites with relaxed temporal stability requirements and its application to GF6/WFI radiometric calibration and validation - Lingling Ma; Yongguang Zhao; Wan Li; Ruoxi Yang; Renfei Wang; Ning Wang; Qijin Han; Xin Lu; Fang Huang; Jianghong Zhao (Remote Sensing of Environment, 2025)

Contributions of natural and anthropogenic factors to summertime thermal environments across different urban scales: An investigation in Chengdu-Chongqing agglomeration, China - Yangtao Wan; Song Yang; Han Han; Yao Mao; Xiao Liu; Meizi You; Xuecheng Fu; Junqing Tang; Ali Cheshmehzangi; Leila Mohaghegh Zahed; Bao-Jie He (Environmental Impact Assessment Review, 2025)

Integrated membrane contactor system using NaOH solution for biogas purification and polyhydroxyalkanoate synthesis via cyanobacteria - Abduljelil W. Sabir; Dong Yun Han; Se Wan Kim; Simon MoonGeun Jung; Ga-Hyeon Kim; Karl Forchhammer; Jong-Hee Kwon; Pyung Soo Lee (Chemical Engineering Journal, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Impact of plant carbon inputs on soil bacterial communities and nitrogen cycle functions in temperate steppe - Yaxuan Cui; Feirong Ren; Yipu Wu; Hao Liu; Zhongjie Sun; Yuzhe Wang; Hayley Peter-Contesse; Shijie Han; Shiqiang Wan; Junqiang Zheng (Plant and Soil, 2025)

Promotion or inhibition? Pathways and impact characteristics analysis of carbon emissions in urban water systems under water-carbon-society multi-factor interactions - Xiaodong Yan; Fei Wang; Xuechun Wan; Mengyu Han; Jingjing Xu (Sustainable Cities and Society, 2025)

Prediction construction for biomass and high-density polyethylene co-gasification via statistical method and machine learning - Jamin Jamir Escalante; Wei-Hsin Chen; Wan Mohd Ashri Wan Daud; Chien-Yuan Su; Po-Han Li (Fuel, 2025)

A fluorescence biosensor for detecting LncRNA MALAT1 based on isothermal amplification by cyclic extension - Xue Shixing; Bu Shengjun; Sun He; Zhang Xinyue; Zhang Xingdong; Zhang Xiaoying; Han Leng; Dai Enyong; Jiayu Wan (Analytica Chimica Acta, 2025)

Correction: Identification of sex-linked markers and genes in Portuguese oyster (Magallana angulata) - Xiaoyan Zhou; Yue Ning; Jingyi Xie; Yi Han; Chaonan Tang; Caiyuan Su; Qijuan Wan; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Frontiers in Marine Science, 2025)

Identification of sex-linked markers and genes in Portuguese oyster (Magallana angulata) - Xiaoyan Zhou; Yue Ning; Jingyi Xie; Yi Han; Chaonan Tang; Caiyuan Su; Qijuan Wan; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Frontiers in Marine Science, 2025)
The Portuguese oyster ( Magallana angulata ) is a valuable aquaculture species with sexual dimorphism in growth and nutritional traits, making it a promising candidate for sex-controlled breeding. However, the genetic mechanisms underlying its sex determination remain poorly understood. This study represents the first population-level investigation to identify sex-linked genetic markers and candidate genes in M. angulata using genome-wide association studies (GWAS) and transcriptomic analysis. A total of 1,613 sex-associated SNPs were identified, primarily located on Chr. 9 (7.99 Mb–10.51Mb). SNP annotation revealed 57 genes around these sex-associated SNPs. Transcriptomic analysis identified 8,635 differentially expressed genes (DEGs) between male and female gonads, of which 12 overlapped with GWAS-identified genes. Among these, four genes ( 5-HTR , ADPKD1-a , SCP , and SLC28A3 ) exhibited strong sex-specific genetic differentiation, with 5-HTR showing the most pronounced association. Further population genetic analysis revealed higher genetic diversity and heterozygosity of 5-HTR in males. Six sex-associated haplotypes based on SNPs within 5-HTR were constructed and validated in an independent population, although with reduced significance, suggesting both continuity and variation in sex determination mechanisms across populations. These findings provide a critical foundation for understanding the genetic basis of sex determination and advancing sex-controlled breeding strategies in M. angulata.

A cooperative discrete artificial bee colony algorithm with Q-learning for solving the distributed permutation flowshop group scheduling problem with preventive maintenance - Wan-Zhong Wu; Hong-Yan Sang; Quan Ke Pan; Qiu-Yang Han; Heng-Wei Guo (Swarm and Evolutionary Computation, 2025)

Application of a comprehensive framework to estimate the risk of agricultural non-point source pollution in China since 2000 - Zhijian Wu; Zhen Zhou; Han Liang; Hanqing Wu; Zhong Liu; Zeyang Xie; Jinqi Zhu; Bofu Zheng; Wei Wan (Journal of Cleaner Production, 2025)

Soybean 7S protein/calcium phosphate complexes for enhanced probiotic delivery and gut microbial regulation - Kaining Han; Guangxin Feng; Tanghao Li; Zhili Wan; Jian Guo; Xiaoquan Yang (Food Bioscience, 2025)

Butterfly-inspired structures on strong and tough metagel for enhanced passive radiative and evaporative cooling - Di Han; Jipeng Fei; Yongping Long; Yuanhang Yang; Anna Lushnikova; Hiba Mhiri; Christophe Ménézo; Man Pun Wan; Hong Li; Xuan Zhang; Bing Feng Ng (Chemical Engineering Journal, 2025)

Upregulation of YY1 in M2 macrophages promotes secretion of exosomes containing hsa-circ-0000326 via super-enhancers to facilitate prostate cancer progression - Han Guan; Huaixiang Tao; Jinguang Luo; Lilin Wan; Hao Hu; Long Chen; Zhiyuan Wen; Yuxuan Tao; Saisai Chen; Mingli Gu (Molecular and Cellular Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Fe3O4@Ag@Pt nanoparticles with multienzyme like activity for total antioxidant capacity assay - Tian Li; Jiaoyuan Fang; Xinying Wan; Han Wang; Liping Zhang; Lan Wang; Xiangjun Qiu; Gaofeng Liang (Food Chemistry, 2025)

Vacancy engineering regulating specific capacitance of supercapacitors in MOF-on-MOF derived CoSe2 quantum dots embedded in carbon and CoSe2 hollow cages - Shuangxing Cui; Yaozong Gu; Yifan Tang; Wan Cui; Guochang Li; Qiuju Zhang; Lei Han (Chemical Engineering Journal, 2025)

Warming‐Induced Plant Species Shifts Lead to Substantial Losses of Wetland Soil Carbon - Baoyu Sun; Ruifeng Sun; Jianjun Xu; Wenjing Gao; Xiaojing Chu; Huilan Yuan; Fangxiu Wan; Liming Yan; Guangxuan Han; Jianyang Xia; Ming Nie (Ecology Letters, 2025)
Wetlands are large reservoirs of soil organic carbon (SOC), storing one‐third of global SOC within 6% of the land surface. However, the feedback direction and magnitude of wetland SOC storage to climate warming remain unclear. Here we present results from an 8‐year (2014–2022) wetland warming experiment in the Yellow River Delta, revealing that wetland SOC storage responds to warming in a phase‐dependent manner. We found that warming initially reduced both carbon input and output but did not change SOC storage. However, SOC storage abruptly decreased by 21.4% in 2020, which persisted over the following 2 years. This occurred mainly due to shifts in the biomass of dominant plant species ( P. australis ) under warming, reducing carbon input, increasing microbial carbon degradation, and resulting in microbial necromass carbon loss. These results highlight the critical role of dominant plant species in driving the wetland soil carbon cycle and its feedback to climate change.

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Seismic response and failure mechanism of caisson: A centrifuge shake-table investigation - Linlu Zhou; Zifei Han; Lei Su; Hua-Ping Wan; Xianzhang Ling (Soil Dynamics and Earthquake Engineering, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Provenance of the Nantuo Formation in the Shennongjia region: Implications for the paleogeographic position of South China in Rodinia - Lisha Hu; Jie Yang; Yuansheng Du; Zuozhen Han; Chao Han; Wei Jin; Le Wan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Evaluation of six latest precipitation datasets for extreme precipitation estimates and hydrological application across various climate regions in China - Yongjing Wan; Daiyuan Li; Jingjing Sun; Mingming Wang; Han Liu (Atmospheric Research, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Nuclear receptor coactive 4-mediated ferritinophagy: a key role of heavy metals toxicity - Wan-Xue Xu; Xue Wen; Yi-Tong Fu; Jie Yang; Han Cui; Rui-Feng Fan (Archives of Toxicology, 2025)

Targets and Potential Mechanism of Chondroitin Sulfate A-selenium Nanoparticle on Kashin-Beck Disease Chondrocytes - Huan Deng; Feidan Deng; Xinyue Wen; Yude Jiang; Abebe Feyissa Amhare; Lichun Qiao; Miaoqian Li; Ping Wan; Jun Wang; Jing Han (Biological Trace Element Research, 2025)

Monitoring the insecticide susceptibility of a newly introduced invasive species, Tuta absoluta (Meyrick), in China - Yi-bo Zhang; Han Li; Peng Han; Xiao-cao Tian; Hao Wang; Li-li Geng; Jie Zhang; Wan-xue Liu; Fang-hao Wan; Raul-Narciso Guedes; Desneux Nicolas; Gui-fen Zhang (Crop Protection, 2025)

Electrochemical destruction of PFAS at low oxidation potential enabled by CeO2 electrodes utilizing adsorption and activation strategies - Xun Liu; Yufei Shu; Yu Pan; Guoshen Zeng; Meng Zhang; Chaoqun Zhu; Youmei Xu; Aling Wan; Mengxia Wang; Qi Han; Bei Liu; Zhongying Wang (Journal of Hazardous Materials, 2025)

Preparation of waste toner-derived magnetic adsorbent for analysis of lead in aqueous and oil-based foods - Long Qin; Yue Wang; Tingjiang Wan; Weian Fan; Han Jiang; Bin Zhang; Yiwei Wu; Xiaoxiao Yu; Chuan Wang (Food Chemistry, 2025)

Unveiling the binding mechanism between wheat arabinoxylan and different molecular weights of wheat glutenins during the dough mixing process - Han Tao; Ya-Ni Li; Hai-Yuan Zhou; Jing-Yi Sun; Meng-Jia Fang; Wan-Hao Cai; Hui-Li Wang (Food Hydrocolloids, 2025)

Adsorption-desorption of propyrisulfuron in six typical agricultural soils of China: Kinetics, thermodynamics, influence of 38 environmental factors and its mechanisms - Zemin Dong; Rendan Zhou; Wengen Wan; Han Li; Wenwen Zhou; Tianqi Wu; Lei Ding; Xiaoqin Xu; Dingwei Liu; Guangwei He; Jing Fan; Yuqi Li; et al. (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Development of electrocoagulation/peracetic acid system to degrade chloramphenicol: Mechanisms and removal efficiency - Bingqian Zheng; Huanhuan Shi; Beibei Wang; Kehao Zhang; Yuran Han; Hongyou Wan; Wei Zhang; Hailong Wang; Liang Mao; Shixiang Gao; Qingguo Huang (Chemical Engineering Journal, 2025)

Designer electron-reservoir single-atom electrocatalyst for efficient carbon dioxide reduction - Wanli Yi; Changsheng Hou; Renyi Li; Yinji Wan; Xuan Zhang; Bing Ma; Wenchao Hu; Shenghui Han; Mulin Qin; Limeng Sun; Qian Wang; Yonggang Wang; et al. (Chemical Engineering Journal, 2025)

Elucidation of the fine structure and anti–breast tumor activity of a glucomannan from the pseudobulbs of Pleione bulbocodioides - Wan-Qi Deng; Shao-Wei Han; Si-Yuan Shao; Shuai Li (Carbohydrate Polymers, 2025)

Spatial heterogeneity in effects of horizontal and vertical environmental features of blocks on land surface temperature: A case study of Shenzhen, China - Yang Wan; Han Du; Xinyu Xie; Xuesong Xu; Haida Tang; Xingkang Chai; Lei Yuan (Building and Environment, 2025)

Potential mechanisms of ZiGongDing in treating HPV-induced cervical intraepithelial neoplasia: a network pharmacology and experimental verification study - Li Wan; Kan Chen; Xiaorong Ma; Lu Han; Qun Xie; Lihong Wang; Xinmei Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A New Pattern of Species Diversification Revealed by Populus on the Qinghai-Tibet Plateau - Jia-Xuan Mi; Fei-Fei Tian; Jin-Liang Huang; Yu-Jie Shi; Jing Li; Fan-Yu Meng; Fang He; Yu Zhong; Han-Bo Yang; Fan Zhang; Liang-Hua Chen; Xue-Qin Wan (Evolutionary Biology, 2025)

New insights into ER stress mediated by ATF6 and IRE1-XBP1 signals in yellow catfish under hypoxia - Ying Wan; Haokun Liu; Junyan Jin; Zhimin Zhang; Yunxia Yang; Xiaoming Zhu; Shouqi Xie; Dong Han (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Evaluation of the detoxification effect and toxicity mechanism of Fenton process for pulping wastewater treatment - Fei Di; Donghui Han; Jinquan Wan; Guang Wang; Yan Wang (Journal of Water Process Engineering, 2025)

Cation-doping tuned flower-like Co-based spinel structure for methane combustion: Structure-effect and reaction pathway confirmation - Xi Zhang; Shuo Yao; Mingjuan Han; Nengjie Feng; Hui Wan; Guofeng Guan (Fuel, 2025)

Cryoprotective effect of wheat starch granular surface proteins on frozen HMW and LMW glutenins: Structure, property and functionality across length scales - Han Tao; Xiao-Han Fang; Meng-Jia Fang; Chao Ding; Wan-Hao Cai; Hui-Li Wang (Food Chemistry, 2025)

Structure-rheological relationship of capillary protein oleogels: The role of particle wettability - Gao-Shang Wang; Long-Yuan Zhang; Guang-Xin Feng; Chuan-Wu Han; Li-Juan Wang; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2025)

Enhancing protein content and lubrication behavior of plant-based milk with microparticulated wheat gluten protein via SS-SH interchange - Feng Liu; Yunqi Huang; Chuanwu Han; Gaoshang Wang; Zhili Wan; Jian Guo; Xiaoquan Yang (Food Hydrocolloids, 2025)

MEHP induced mitochondrial damage by promoting ROS production in CIK cells, leading to apoptosis, autophagy, cell cycle arrest - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Optimizing high-volume evacuator usage: A quantitative analysis of aerosol control in dental procedures - Chenxue Song; Xiaohong Zheng; Lei Han; Qinjie Wan; Jiayu Huang; Zhen Ding; Hua Qian (Building and Environment, 2025)

Metabolomics Revealed Cadmium Exposure Associated with Alterations in Serum Metabolism in Children - Miaoqian Li; Ping Wan; Lichun Qiao; Xinyue Wen; Huan Deng; Xue Lin; Jingke Lei; Jing Han (Biological Trace Element Research, 2025)

Cold storage of Aphidoletes aphidimyza can extend offspring larval development period and improve its predation ability - Xuli Zhu; Qingting Yuan; Weiqiang Tian; Maofa Yang; Xiaoyan Wang; Xiaobin Han; Jun Wan; Huizi Wu; Xiaofei Yu (Crop Protection, 2025)

Exploring the influence of block environmental characteristics on land surface temperature and its spatial heterogeneity for a high-density city - Yang Wan; Han Du; Lei Yuan; Xuesong Xu; Haida Tang; Jianfeng Zhang (Sustainable Cities and Society, 2025)

Progress and challenges of spinel materials for catalytic combustion of methane - Xi Zhang; Xiaodi Zhang; Lingling Ren; Mingjuan Han; Nengjie Feng; Hui Wan; Guofeng Guan (Fuel, 2025)

Low-temperature glucose foaming to construct three-dimensionally porous bulk CoMo catalyst for thiophene hydrodesulfurization - Yeqiang Du; Longzhou Ren; Wenjing Song; Ziqi Wan; Qinqin Zhang; Liancheng Bing; Fang Wang; Guangjian Wang; Haitao Fu; Dezhi Han (Fuel, 2025)

New fast imaging techniques for electrical source transient electromagnetic data: Approaches and application - Yu-lian Zhu; Wei-ying Chen; Wan-ting Song; Si-xu Han (Computers & Geosciences, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Environmental salinity differentiates responses to acute hypothermal stress in milkfish - Naveen Ranasinghe; Yi-Ren Huang; Wan-Hua Wu; Shi-Shien Lee; Chuan-Wen Ho; Tsung-Han Lee; Kuei-Yang Hsiao (Science of The Total Environment, 2024)

Investigation of nitrogen conversion in ditch-treated greywater: Contributions of biochar and aeration - Ronggao Qin; Meidan Lai; Guangzhu Cao; Yi Qiang; Wan Xu; Yiming Xie; Rui Zuo; Kexue Han (Journal of Environmental Chemical Engineering, 2024)

Enhanced biochemical treatment of pulping wastewater by Fenton process: Water quality optimization and detoxification efficiency - Fei Di; Donghui Han; Jinquan Wan; Guang Wang; Yan Wang (Journal of Environmental Chemical Engineering, 2024)

A comprehensive review of critical factors affecting green ammonia synthesis by electrochemical process - Cheng-Yi Li; Shen-Wei Chu; Chia-Yun Ho; Han-Jung Chang; Terng-Jou Wan (Journal of Environmental Chemical Engineering, 2024)

Experimental study on optimizing tailwater reinjection technology for weakly consolidated sandstone geothermal reservoirs - Jieqin Xia; Hong Tian; Bin Dou; Jun Zheng; Xiaotian Lai; Han Zhang; Wan Sun (Fuel, 2024)

Enhanced creaminess of plant-based milk via enrichment of papain hydrolyzed oleosomes - Biao Li; Chuanwu Han; Guangxin Feng; Jian Guo; Zhili Wan; Xiaoquan Yang (Food Research International, 2024)

Protective mechanisms of Hovenia dulcis Thunb extracts on acute alcoholism and liver injury - Honglin Lan; Zhouya Bai; Denglin Luo; Yanli Wang; Mengyuan Geng; Xingguo Li; Yunhui Zhang; Jiahao Wan; Yanbin Wang; Sihai Han (Food Bioscience, 2024)

Methylparaben changes the community composition, structure, and assembly processes of free-living bacteria, phytoplankton, and zooplankton - Man Wang; Shengxing Wang; Huabing Li; Zhendu Mao; Yiwei Lu; Yunshan Cheng; Xiaotong Han; Yujing Wang; Yanru Liu; Shiqiang Wan; Li-Jun Zhou; Qinglong L. Wu (Environmental Research, 2024)

Activating NiO nanorods array via nitrogen ion implantation for enhanced alkaline hydrogen evolution - Jaerim Kim; Sang-Mun Jung; Hyeonae Im; Hyeonwoong Hwang; Dong-Seok Kim; Gi Wan Jeon; Yong-Tae Kim; Jeong Woo Han; Jong Kyu Kim (Chemical Engineering Journal, 2024)

Decadal trends of black carbon and heavy metal accumulation in a lake sediment core from central China: A historical perspective - Changlin Zhan; Dejun Wan; Yongming Han; Jiaquan Zhang; Shan Liu; Hongxia Liu; Tianpeng Hu; Wensheng Xiao; Junji Cao; Dong Li (CATENA, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Exploring the application of ant colony optimization in path planning for Unmanned Surface Vehicles - Han Heng; Mohamad Hazwan Mohd Ghazali; Wan Rahiman (Ocean Engineering, 2024)

Effect of climate warming on subsurface temperature in basins with topography-driven groundwater flow - Yi-Peng Zhang; Xiao-Wei Jiang; Shemin Ge; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Lizhi Wang; Qing Liu; Li Wan (Journal of Hydrology, 2024)

Stabilization of oil-water interface by non-interfacial adsorbed native starch granules using depletion attraction - Chuanwu Han; Guangxin Feng; Shouwei Yin; Gaoshang Wang; Jinmei Wang; Zhili Wan; Jian Guo; Xiaoquan Yang (Food Hydrocolloids, 2024)

Dermal toxicity studies of 1,2-benzisothiazolin-3-one (CAS number: 2634-33-5) in Sprague-Dawley rats - Joon-Goo Lee; Muthuchamy Maruthupandy; ChulBeom Park; Seol-Hee Moon; Soyoung Yang; Misook Jung; Sun Hee Park; Beom Seok Han; Wan-Seob Cho (Food and Chemical Toxicology, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Effects of nitrile compounds on the structure and function of soil microbial communities as revealed by metagenomes - Ting Gao; Yiwang Wang; Jinlong Lai; Fuli Wang; Ge Yao; Shaoheng Bao; Jiajia Liu; Xiukun Wan; Chang Chen; Yunfei Zhang; Hui Jiang; Shijie Jiang; et al. (Environmental Research, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Photoelectron-transfer-effect grafting: Validation of a generalized strategy for fluorescence and photoelectrochemical dual-mode detection of hydrogen sulfide - Xiao-Jie Yu; Xiao-Yan Wan; Yu-Ting Shen; Deng-Bao Zhang; Xian-Jing Zhou; De-Man Han; Feng-Zao Chen (Analytica Chimica Acta, 2024)

Comprehensive assessment of refined greenhouse gas emissions from China's livestock sector - Yun Huang; Han Liang; Zhijian Wu; Zeyang Xie; Zhong Liu; Jinqi Zhu; Bofu Zheng; Wei Wan (Science of The Total Environment, 2024)

Improved forest height mapping using multibaseline low-frequency PolInSAR data based on effective selection of dual-baseline combinations - Yanzhou Xie; Haiqiang Fu; Jianjun Zhu; Changcheng Wang; Qinghua Xie; Jie Wan; Wentao Han (Remote Sensing of Environment, 2024)

Experimental study on the hydrodynamic of foldable-wing unmanned aerial-underwater vehicles during water-exit process - Zhaoliang Han; Jian Cao; Ye Li; Hongwei Li; Zipeng Du; Jinyu Fu; Lei Wan (Ocean Engineering, 2024)

Which biofilm reactor is suitable for degradation of 2,4-dimethylphenol, focusing on bacteria, algae, or a combination of bacteria-algae? - Jingxin Shi; Ning Wan; Shuhui Yang; Yuanyuan Yang; Hongjun Han (Journal of Hazardous Materials, 2024)

Supplementation with a phenolic-rich fraction from Ilex kudingcha improves inflammatory stress, gastrocnemius weights, and foreleg muscle grip strength in murine squamous cell carcinoma (SCC7)-bearing mice - Han-Chen Chao; Wan-Li Yang; Li-Wha Wu; Jin-Yuarn Lin (Food Bioscience, 2024)

Quantifying the impact of factors on soil available arsenic using machine learning - Zhaoyang Han; Jun Yang; Yunxian Yan; Chen Zhao; Xiaoming Wan; Chuang Ma; Huading Shi (Environmental Pollution, 2024)

Improvement of methane reforming Ni-based catalyst stability by controlling the unsaturated coordination aluminum in metakaolinite - Libo Han; Jiadong Liu; Hui Yang; Hao Qu; Ruijue Hu; Haiquan Su; Yue Su; Lili Wan (Chemical Engineering Journal, 2024)

Effects of 6-methoxybenzoxazolinone (6-MBOA) on animals: state of knowledge and open questions - Jia-Yi Shi; Ke-Han Gu; Sheng-Mei Yang; Wan-Hong Wei; Xin Dai (The Science of Nature, 2024)

HER2 mutations in advanced cervical neuroendocrine carcinoma: implications for trastuzumab deruxtecan therapy - Wan-Ru Chao; Ming-Yung Lee; Gwo-Tarng Sheu; Yi-Ju Lee; Huang-Pin Shen; Chih-Ping Han (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Mechanism of HDAC1 Regulating Iron Overload-Induced Neuronal Oxidative Damage After Cerebral Hemorrhage - Jing Han; Jinnan Zhang; Xiaojuan Yao; Meng Meng; Yahui Wan; Yan Cheng (Molecular Neurobiology, 2024)

Sources and factors influencing lacustrine carbon burial over the last century: case study of Yinjia Lake, central China - Changlin Zhan; Dejun Wan; Yongming Han; Shan Liu; Jiaquan Zhang; Hongxia Liu; Tianpeng Hu; Wensheng Xiao; Junji Cao (Journal of Paleolimnology, 2024)

Decoded EEG neurofeedback-guided cognitive reappraisal training for emotion regulation - Linling Li; Xueying Gui; Gan Huang; Li Zhang; Feng Wan; Xue Han; Jianhong Wang; Dong Ni; Zhen Liang; Zhiguo Zhang (Cognitive Neurodynamics, 2024)

Petrogenesis of Neoarchean granitic gneisses from the Daqishan area of the Dabie orogen and implications for the early crustal evolution of the Northern Yangtze Craton - Lingyao Kong; Xiang Xing; Qingsen Han; Hua Luo; Pan Guo; Xin Deng; Jun Wan; Chao Chen; Chengxin Liu (International Geology Review, 2024)

The transcriptional changes of LrgA discriminates the responsiveness of Staphylococcus aureus towards blue light from that of photodynamic inactivation - Ruili Yang; Yi Xu; Jinchun Xu; Yali Li; Xiaoxiao Wan; Rui Kong; Chao Ding; Han Tao; Hui-Li Wang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Metagenomics reveals the potential transmission risk of resistomes from urban park environment to human - Xiaochen Wang; Yuan Qian; Yu Wang; Sijie Wang; Jie Bi; Chenwei Shi; Qian Han; Ruijun Wan-Yan; Qiaoling Yu; Huan Li (Journal of Hazardous Materials, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Versatile additive for enhancing the stability of Zn Anode: Pyrrolidine-based ionic liquid - Kailimai Su; Hong Zhang; Yan Wang; Xingyun Zhang; Yongbiao Mu; Zhibin Lu; Ye Han; Shanhong Wan; Junwei Lang (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Modeling of Hydro-mechanical Coupled Fracture Propagation in Quasi-brittle Rocks Using a Variational Phase-Field Method - Shi-fan Liu; Wei Wang; Yun Jia; Han-bing Bian; Wan-qing Shen (Rock Mechanics and Rock Engineering, 2024)

Actn2 defects accelerates H9c2 hypertrophy via ERK phosphorylation under chronic stress - Kang Wang; Ye Wang; Hua Wan; Jie Wang; Li Hu; Shuainan Huang; Mingchen Sheng; Jiayi Wu; Xing Han; Youjia Yu; Peng Chen; Feng Chen (Genes & Genomics, 2024)

Emamectin benzoate exposure induced carp kidney injury by triggering mitochondrial oxidative stress to accelerate ferroptosis and autophagy - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Pesticide Biochemistry and Physiology, 2024)

Cadaverine and putrescine exposure influence carbon and nitrogen cycling genes in water and sediment of the Yellow River - Wanghong Su; Qiaoling Yu; Jiawei Yang; Qian Han; Sijie Wang; Petr Heděnec; Xiaochen Wang; Ruijun Wan-Yan; Huan Li (Journal of Environmental Sciences, 2024)

Emission and optical characteristics of brown carbon in size-segregated particles from three types of Chinese ships - Fengqin Yang; Fan Zhang; Zeyu Liu; Yingjun Chen; Yan Zhang; Can Wu; Yali Lei; Shijie Liu; Binyu Xiao; Xinyi Wan; Yubao Chen; Yong Han; et al. (Journal of Environmental Sciences, 2024)

Elemental differentiation and isotopic fractionation during space weathering of Chang’E-5 lunar soil - Qingshang Shi; Yongsheng He; Jian-Ming Zhu; Yang Wang; Yang Wang; Hongjie Wu; Peijie Wang; Ruyi Yang; Aiying Sun; Yinchu Zhang; Guangliang Wu; Ruoqi Wan; et al. (Geochimica et Cosmochimica Acta, 2024)

An insight into trichomes-deficiency and trichomes-rich black teas by comparative metabolomics: The impact of oxidized trichomes on metabolic profiles and infusion color - Piaopiao Long; Shengxiao Su; Mingchun Wen; Xuyang Liu; Zisheng Han; Jia-Ping Ke; Yu Zhou; Mengting Zhu; Yong Cheng; Yundong Shao; Xiaochun Wan; Liang Zhang (Food Research International, 2024)

Boosted scavenger-free photocatalytic H2O2 production over alkali-doped poly(heptazine imide) under controlled solution conditions - Ming Fang; Biao Wang; Guanhua Wan; Hui Cao; Chunfeng Wang; Peijiang Cao; Shun Han; Deliang Zhu; Wenjun Liu (Chemical Engineering Journal, 2024)

Differential eco-toxicological responses toward Eisenia fetida exposed to soil contaminated with naphthalene and typical metabolites - Mingyang Jing; Guangye Han; Jingqiang Wan; Wansong Zong; Rutao Liu (Environmental Science and Pollution Research, 2024)

Influence of Pteris vittata-maize intercropping on plant agronomic parameters and soil arsenic remediation - Tianying Wan; Xiangwei Dong; Lihua Yu; Dandan Li; Haozhan Han; Shuxin Tu; Jin Wan (Chemosphere, 2024)

Distinct response patterns of soil micro-eukaryotic communities to early-season and late-season precipitation in a semiarid grassland - Yanyan Yu; Jingyi Ru; Binghai Lei; Shijie Han; Shiqiang Wan; Junqiang Zheng (Soil Biology and Biochemistry, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Prediction of pressure drop in solid-liquid two-phase pipe flow for deep-sea mining based on machine learning - Chuyi Wan; Hongbo Zhu; Shengpeng Xiao; Dai Zhou; Yan Bao; Xu Liu; Zhaolong Han (Ocean Engineering, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

The short-term effects of individual and mixed ambient air pollutants on suicide mortality: A case-crossover study - Xinyao Lian; Yaqi Wang; Jianhui Guo; Xiaoyu Wan; Xinyao Ye; Jinyi Zhou; Renqiang Han; Hao Yu; Shaodan Huang; Jing Li (Journal of Hazardous Materials, 2024)

Insight into the promoted recrystallization and water distribution of bread by removing starch granule - surface and - associated proteins during storage - Han Tao; Li-Jiao Huang; Shuo-qian Li; Fan Lu; Wan-Hao Cai; Hui-Li Wang (Food Chemistry, 2024)

Chemical, sensory and biological variations of black tea under different drying temperatures - Shengxiao Su; Piaopiao Long; Qing Zhang; Mingchun Wen; Zisheng Han; Feng Zhou; Jiaping Ke; Xiaochun Wan; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2024)

An untargeted metabolomics study of cardiac pathology damage in rats caused by low selenium diet alone or in combination with T-2 toxin - Xue Lin; Lichun Qiao; Haobiao Liu; Miaoye Bao; Huan Deng; Lianxu Jia; Xinyue Wen; Feidan Deng; Ping Wan; Yizhen Lyu; Jing Han (Food and Chemical Toxicology, 2024)

Exploring mycorrhizal diversity in sympatric mycoheterotrophic plants: a comparative study of Monotropastrum humile var. humile and M. humile var. glaberrimum - Ren-Cheng Liu; Wan-Rou Lin; Pi-Han Wang (Mycorrhiza, 2024)

Plant diversity decreases greenhouse gas emissions by increasing soil and plant carbon storage in terrestrial ecosystems - Pengfei Dang; Miaomiao Zhang; Xinli Chen; Michel Loreau; J. Emmett Duffy; Xin'e Li; Shuyue Wen; Xiaoqing Han; Lechen Liao; Tiantian Huang; Chenxi Wan; Xiaoliang Qin; et al. (Ecology Letters, 2024)
The decline in global plant diversity has raised concerns about its implications for carbon fixation and global greenhouse gas emissions (GGE), including carbon dioxide (CO 2 ), nitrous oxide (N 2 O) and methane (CH 4 ). Therefore, we conducted a comprehensive meta‐analysis of 2103 paired observations, examining GGE, soil organic carbon (SOC) and plant carbon in plant mixtures and monocultures. Our findings indicate that plant mixtures decrease soil N 2 O emissions by 21.4% compared to monocultures. No significant differences occurred between mixtures and monocultures for soil CO 2 emissions, CH 4 emissions or CH 4 uptake. Plant mixtures exhibit higher SOC and plant carbon storage than monocultures. After 10 years of vegetation development, a 40% reduction in species richness decreases SOC content and plant carbon storage by 12.3% and 58.7% respectively. These findings offer insights into the intricate connections between plant diversity, soil and plant carbon storage and GGE—a critical but previously unexamined aspect of biodiversity–ecosystem functioning.

Food polyphenols and Maillard reaction: regulation effect and chemical mechanism - Zisheng Han; Mengting Zhu; Xiaochun Wan; Xiaoting Zhai; Chi-Tang Ho; Liang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Enhancing intercropping sustainability: Manipulating soybean rhizosphere microbiome through cropping patterns - Pengfei Dang; Chen Lu; Tiantian Huang; Miaomiao Zhang; Ning Yang; Xiaoqing Han; Chunhong Xu; Shiguang Wang; Chenxi Wan; Xiaoliang Qin; Kadambot H.M. Siddique (Science of The Total Environment, 2024)

Anti-inflammatory activity of organic acids from the seeds of Phaseolus lunatus L. - Kun Li; Jin-hui Bian; Heng Wu; Ya-lan Wang; Yun-jia Feng; Jia Nie; Na Chen; Han Yu; Wan Li; Yu-zhu Tan; Guang-hua Lu (Phytochemistry Letters, 2024)

Numerical analysis of coarse particle two-phase flow in deep-sea mining vertical pipe transport with forced vibration - Chuyi Wan; Shengpeng Xiao; Dai Zhou; Hongbo Zhu; Yan Bao; Tingping Li; Jiahuang Tu; Muwanguzi Stephen Kyazze; Zhaolong Han (Ocean Engineering, 2024)

Improvement of biotic nitrate reduction in constructed photoautotrophic biofilm-soil microbial fuel cells - Yu Cheng; Jue Ding; Jiahui Wan; Li Tang; Akaninyene Joseph; Muhammad Usman; Ningyuan Zhu; Yanxia Zhang; Han Sun; Eldon R. Rene; Marton Lendvay; Yiping Li (Journal of Environmental Management, 2024)

A synergistic polyelectrolytes-Zr-MOF hydrated construction graphene oxide nanofiltration with enhanced dye wastewater remediation - Lan Ma; Guilan Zhang; Yan Wan; Teng Wang; Xinyan Li; Yin Zhang; Tianfeng He; Rui Han; Liyun Zhang (Journal of Environmental Chemical Engineering, 2024)

Evaluating salivary aerosol spread and contamination risks during dental procedures in an open-plan clinic - Jiayu Huang; Xiaohong Zheng; Lei Han; Qinjie Wan; Danting Luo; Zhiyong Shu; Chenxue Song; Hua Qian (Journal of Aerosol Science, 2024)

Linear and nonlinear rheological characterization of capillary protein oleogels as potential fat replacers: Comparison with high internal-phase emulsions - Gao-Shang Wang; Qing Li; Guang-Xin Feng; Chuan-Wu Han; Jian Guo; Jin-Mei Wang; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2024)

Modulations of ocean-atmosphere interactions on squid abundance over Southwest Atlantic - Chia-Ying Ko; Yu-Chi Lee; Yi-Chi Wang; Huang-Hsiung Hsu; Chun Hoe Chow; Ruei-Gu Chen; Tsung-Han Liu; Chih-Shin Chen; Tai-Sheng Chiu; Don-Hsieh Chiang; Ren-Fen Wu; Wan-Ling Tseng (Environmental Research, 2024)

From theory to practice: Dissociation of AsMA under reactive metal perturbations for the harmlessness and resourcefulness of copper slag - Xingyuan Wan; Kaixi Jiang; Ting'an Zhang; Kun Wang; Han Yang; Shengnan Lin (Chemical Engineering Journal, 2024)

Arbuscular mycorrhizal fungal diversity associated with an endangered species, Chamaecyparis formosensis, in the nature habitat - Tzu-Chao Lin; Wan-Rou Lin; Lei-Chen Lin; Pi-Han Wang (Tropical Ecology, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Consistent efficacy outcomes between phase 2 and phase 3 trials in Crohn’s disease or ulcerative colitis in adults: a meta-analysis - Ziqi Wan; Qingwei Jiang; Runing Zhou; Xiang Li; Wei Han; Bing Xu; Mingyue Guo; Gechong Ruan; Xiaoyin Bai; Guanqiao Li; Hong Yang (Inflammation Research, 2024)

Multimodal and hemispheric graph-theoretical brain network predictors of learning efficacy for frontal alpha asymmetry neurofeedback - Linling Li; Yutong Li; Zhaoxun Li; Gan Huang; Zhen Liang; Li Zhang; Feng Wan; Manjun Shen; Xue Han; Zhiguo Zhang (Cognitive Neurodynamics, 2024)

Mechanism of organic phosphorus transformation and its impact on the primary production in a deep oligotrophic plateau lake during stratification - Xiaotong Han; Fan Xun; Xianlong Zhu; Cheng Zhao; Wenlei Luo; Yanru Liu; Man Wang; Di Xu; Shiqiang Wan; Qinglong L. Wu; Peng Xing (Water Research, 2024)

Corrigendum to “Urinary biomarkers of exposure to organophosphate, pyrethroid, neonicotinoid insecticides and oxidative stress: A repeated measurement analysis among pregnant women” [Sci. Total Environ. volume 912, 2024, 169565] - Aizhen Wang; Yanjian Wan; Wei Qi; Gaga Mahai; Xi Qian; Tongzhang Zheng; Yuanyuan Li; Shunqing Xu; Han Xiao; Wei Xia (Science of The Total Environment, 2024)

Nighttime warming and nitrogen addition effects on the microclimate of a freshwater wetland dominated by Phragmites australis - Yunpeng Guo; Jian Song; Jiayin Feng; Hongpeng Wang; Jinhua Zhang; Jingyi Ru; Xiaopan Wang; Xu Han; Huixia Ma; Yaru Lyu; Wenjing Ma; Chao Wang; et al. (Science of The Total Environment, 2024)

Revealing the variances in color formation and bioactivities of seven catechin monomers throughout the enzymatic reaction by colorimetric and mass spectrometry - Wei Hu; Mingchun Wen; Zisheng Han; Xue-Ling Gao; Jia-Ping Ke; Mengting Zhu; Xinlin Wei; Yong Cheng; Xiaochun Wan; Yundong Shao; Liang Zhang (Food Research International, 2024)

Unveiling the binding mechanism between starch granule-surface proteins and glutenins during dough mixing process - Chao Ding; Wan-Hao Cai; Jing-Yi Sun; Han Tao; Hui-Li Wang (Food Hydrocolloids, 2024)

Using a novel vector length stability index (VLSI) to evaluate soil aggregate stability: A preliminary study - Fan Ma; Liang Liu; Xinsheng Han; Yueling Wang; Haixia Wan; Jinwen Xia; Xianghui Lu (CATENA, 2024)

Cotton-derived three-dimensional carbon fiber aerogel with hollow nanocapsules and ultrahigh adsorption efficiency in dynamic sewage treatment system - Peng Zhang; Lei Zhang; Xiaoyan Yang; Mingming Chi; Yue Han; Zehao Zhang; Changhua Liu; Wubo Wan; Xiaoming Zhao (Bioresource Technology, 2024)

Origins and health risk assessment of PAHs/APAHs/NPAHs/OPAHs in PM2.5 at a background site in North China Plain: Implications for crude oil emissions - Xiongfei Zhang; Hongliang Gao; Anan Qi; Shengfei Duan; Wan Zhang; Yan Zhang; Qi Huang; Tong Zhao; Guangxuan Han; Wenxing Wang; Lingxiao Yang (Atmospheric Pollution Research, 2024)

Gastrodin Regulates PI3K/AKT-Sirt3 Signaling Pathway and Proinflammatory Mediators in Activated Microglia - Han-Jun Zuo; Peng-Xiang Wang; Xue-Qi Ren; Hao-Long Shi; Jin-Sha Shi; Tao Guo; Cheng Wan; Juan-Juan Li (Molecular Neurobiology, 2024)

Interspecific occupancy-abundance relationship of benthic diatoms changes seasonally with attachment mode in a tropical river - Lin Tan; Yuting Liu; Muqi Shen; Guifeng Wei; Linglin Wan; Quehui Tang; Bo-Ping Han (Hydrobiologia, 2024)

Estimating and projecting the effects of urbanization on the forest habitat quality in a highly urbanized area - Mingxuan Wan; Yiwen Han; Youngkeun Song; Shizuka Hashimoto (Urban Forestry & Urban Greening, 2024)

Exposure to different surface-modified polystyrene nanoparticles caused anxiety, depression, and social deficit in mice via damaging mitochondria in neurons - Yuhan Ma; Dihui Xu; Zicheng Wan; Ziyang Wei; Zining Chen; Yuheng Wang; Xiaodong Han; Yabing Chen (Science of The Total Environment, 2024)

Study on the impact of reducing fossil energy use on China's existing economic structure under carbon neutrality goals - Jianmin Wang; Lixiang Wang; Han Wan (Journal of Cleaner Production, 2024)

Silver nanoparticles induce iron accumulation-associated cognitive impairment via modulating neuronal ferroptosis - Xuedi Zhai; Weici Yan; Shuhui Liu; Liang Tian; Yidan Zhang; Yiwei Zhao; Yebo Ni; Han Shen; Jianshu Wang; Zhongxiao Wan; Fei Jiang; Lili Xin (Environmental Pollution, 2024)

Targeted Metabolomic Biomarkers for Stroke Subtyping - Eung-Joon Lee; Da Jung Kim; Dong-Wan Kang; Wookjin Yang; Han-Yeong Jeong; Jeong-Min Kim; Sang-Bae Ko; Seung-Hoon Lee; Byung-Woo Yoon; Joo-Youn Cho; Keun-Hwa Jung (Translational Stroke Research, 2024)

Genetic diversity and population relationships in wild Korean black raspberry (Rubus coreanus Miq.) based on microsatellite markers: establishing a fruit tree breeding strategy - Sung-Kyung Han; Hanna Shin; Jei-Wan Lee; Kyung-Nak Hong; Ji-Young Ahn (Horticulture, Environment, and Biotechnology, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

MMF-CNN: a multimodal fusion CNN network for winter wheat extraction incorporating active and passive time series data - Jingyi Chen; Haifeng Han; Mingming Xu; Jianhua Wan; Shanwei Liu (International Journal of Remote Sensing, 2024)

Review of the research status on the transmission and diffusion characteristics of indoor viral aerosol particles - Yaxin Huang; Jie Wan; Sen Han; Yu Li (Environmental Science and Pollution Research, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

New insights into toxicity reduction and pollutants removal during typical treatment of papermaking wastewater - Fei Di; Donghui Han; Jinquan Wan; Guang Wang; Bin Zhu; Yan Wang; Shou Yang (Science of The Total Environment, 2024)

New policy framework for circular economy in South Korea: Achieving both management and chemical recycling of polymeric waste via pyrolysis reaction - Tae Uk Han; Jun-Gu Kang; Tae-Wan Jeon (Resources, Conservation and Recycling, 2024)

Diffusion kinetic processes and release risks of trace metals in plateau lacustrine sediments - Xiang Gu; Xiaotong Han; Peng Xing; Di Xu; Shiqiang Wan; Qinglong L. Wu; Fengchang Wu (Journal of Hazardous Materials, 2024)

Pelargonidin alleviates acrolein-induced inflammation in human umbilical vein endothelial cells by reducing COX-2 expression through the NF-κB pathway - Youping Wan; Han Yang; Guoping Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effect of saline water drip irrigation on tomato yield and quality in semi-humid area and arid area of China - Xiaoyu Han; Dan Li; Yaohu Kang; Shuqin Wan (Irrigation Science, 2024)

Microbiota-mediated metabolic perturbations in the gut and brain of mice after microplastic exposure - Sheng-Han Lee; Wan-Yu Lin; Tsun-Jen Cheng (Chemosphere, 2024)

Effects of light spectra on the ovarian maturation and maternal immunity in the little yellow croaker (Larimichthys polyactis) - Ming Ming Han; Wei Zhan; Xiao Liang; Dan Dan Guo; Wan Tu Xu; Bao Lou (Aquaculture, 2024)

Urinary biomarkers of exposure to organophosphate, pyrethroid, neonicotinoid insecticides and oxidative stress: A repeated measurement analysis among pregnant women - Aizhen Wang; Yanjian Wan; Wei Qi; Gaga Mahai; Xi Qian; Tongzhang Zheng; Yuanyuan Li; Shunqing Xu; Han Xiao; Wei Xia (Science of The Total Environment, 2024)

Increasing terrigenous input into the continental margin seawater during the late Ediacaran, North China - Jie Yang; Yuansheng Du; Zuozhen Han; Lisha Hu; Zihu Zhang; Le Wan; Zuoxun Zeng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Three-dimensional inter-basin groundwater flow toward a groundwater-fed stream: Identification, partition, and quantification - Peng-Fei Han; Xu-Sheng Wang; Yangxiao Zhou; Zhi Yang; Li Wan; Jinsong Chen; Xiao-Wei Jiang (Journal of Hydrology, 2024)

Electrosynthesis of peracetic acid using in-situ generated H2O2 enabled by carbon-based bifunctional electrodes - Zeheng Lin; Felice; George E.P. O'Connell; Tao Wan; Ding Zhang; Lingyi Peng; Dewei Chu; Xunyu Lu; Zhaojun Han (Chemical Engineering Journal, 2024)

Clinical outcomes and immunological features of COVID-19 patients receiving B-cell depletion therapy during the Omicron era - Chan Mi Lee; Minji Kim; Seong-wook Park; Chang Kyung Kang; Pyoeng Gyun Choe; Nam Joong Kim; Hyeon Jae Jo; Hyun Mu Shin; Chang-Han Lee; Hang-Rae Kim; Wan Beom Park; Myoung-don Oh (Infectious Diseases, 2024)

Quantitative evaluation of the impact of hydrological forecasting uncertainty on reservoir real-time optimal operation - Feilin Zhu; Yaqin Wang; Bojun Liu; Qing Cao; Mingyu Han; Yurou Zeng; Meiyan Lin; Lingqi Zhao; Xinrong Wang; Zhiqi Wan; Ping-an Zhong (Stochastic Environmental Research and Risk Assessment, 2024)

Luteolin inhibits the JAK/STAT pathway to alleviate auditory cell apoptosis of acquired sensorineural hearing loss based on network pharmacology, molecular docking, molecular dynamics simulation, and experiments in vitro - Fang Guo; Yingyuan Guo; Dejun Zhang; Zeming Fu; Shuang Han; Yining Wan; Guofang Guan (Toxicology and Applied Pharmacology, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Tartaric acid coupled with gibberellin improves remediation efficiency and ensures safe production of crops: A new strategy for phytoremediation - Teng-yue Yuan; Da-juan Wan; Wen-jun Yang; Jiao-feng Gu; Hang Zhou; Peng Zeng; Bo-han Liao (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Modified toxic potential of multi-walled carbon nanotubes to zebrafish (Danio rerio) following a two-year incubation in water - Youn-Joo Jung; Thillaichidambaram Muneeswaran; Jin Soo Choi; Sumin Kim; Jong Hun Han; Wan-Seob Cho; June-Woo Park (Journal of Hazardous Materials, 2024)

Synergistic reinforcement of polylactic acid/wood fiber composites by cellulase and reactive extrusion - Han Wan; Ce Sun; Chang Xu; Baiwang Wang; Yang Chen; Yueqiang Yang; Haiyan Tan; Yanhua Zhang (Journal of Cleaner Production, 2024)

Eupatilin inhibits xanthine oxidase in vitro and attenuates hyperuricemia and renal injury in vivo - Guitao Xu; Lele Wu; Hongxuan Yang; Tianfeng Liu; Ying Tong; Jiliang Wan; Bin Han; Lin Zhou; Xuguang Hu (Food and Chemical Toxicology, 2024)

RETRACTED: Ancient forest plants possess cytotoxic properties causing liver cancer HepG2 cell apoptosis - Xiaochen Yue; Nyuk Ling Ma; Jiateng Zhong; Han Yang; Huiling Chen; Yafeng Yang; Su Shiung Lam; Lijun Yan; Bjarne Styrishave; Tomasz Maciej Ciesielski; Wan-Xi Peng; Christian Sonne (Environmental Research, 2024)

Contrasting behavior of K isotopes in modern and fossil groundwater: Implications for K cycle and subsurface weathering - Tao-Tao Ji; Xiao-Wei Jiang; Guilin Han; Xiaoqiang Li; Li Wan; Ze-Zhou Wang; Huaming Guo; Zhangdong Jin (Earth and Planetary Science Letters, 2024)

Long-Life flexible mild Ag-Zn fibrous battery with bifunctional gel electrolyte - Yanzhe Zhu; Jiajun Fan; Shuo Zhang; Ziheng Feng; Chao Liu; Renbo Zhu; Yunjian Liu; Peiyuan Guan; Mengyao Li; Zhaojun Han; Tao Wan; Jianbo Tang; et al. (Chemical Engineering Journal, 2024)

Fast ion/electron transport enabled by MXene confined bimetallic sulfides with heterostructure toward highly effective lithium/sodium storage - Yun-Lei Hou; Jing-Zhou Chen; Bo-Han Zhang; Hua-Ying Wang; Wan-Xin Wen; Dong-Lin Zhao (Chemical Engineering Journal, 2024)

Multilayer composite membranes composed of carbon molecular sieve membranes sandwiched between stacked zeolite nanosheets - Dong Yun Han; Ah Hyun Lee; Su Kyung Kang; Se Wan Kim; Woo Chul Kwak; In-Seok Jeon; Seunghwa Yang; Pyung Soo Lee (Chemical Engineering Journal, 2024)

Action mechanism of the potential biocontrol agent Brevibacillus laterosporus SN19-1 against Xanthomonas oryzae pv. oryzae causing rice bacterial leaf blight - Xin-xin Su; Tian-tian Wan; Yong-dong Gao; Song-han Zhang; Xiu Chen; Lan-qi Huang; Wei Wang (Archives of Microbiology, 2024)

Progress in phytoremediation of chromium from the environment - Lingzhuo Han; Haiping Gu; Wenjie Lu; Hanyin Li; Wan-xi Peng; Nyuk Ling Ma; Su Shiung Lam; Christian Sonne (Chemosphere, 2023)

Strain-specific metabolomic diversity of Lactiplantibacillus plantarum under aerobic and anaerobic conditions - Su-Hyun Kim; Digar Singh; Seul-Ah Kim; Min Jeong Kwak; Donghyun Cho; Juewon Kim; Jong-Hwa Roh; Wan-Gi Kim; Nam Soo Han; Choong Hwan Lee (Food Microbiology, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Endophytic bacterium Bacillus cereus affects host litter decomposition by regulating soil microbial structure and phosphate mineralization - Haijing Hu; Rumeng Ye; Lu Pang; Han Jiang; Kai Tian; Yang Gao; Yanli Ji; Pengwei Wan; Junbo Yang; Xiaoming Zou; Xingjun Tian (Applied Soil Ecology, 2023)

Eif2s3y alleviated LPS-induced damage to mouse testis and maintained spermatogenesis by negatively regulating Adamts5 - Yunxiang Li; Wenping Wu; Wenjing Xu; Yuqi Wang; Shicheng Wan; Wenbo Chen; Donghui Yang; Mengfei Zhang; Xiaojie Wu; Xinchun Yang; Xiaomin Du; Congliang Wang; et al. (Theriogenology, 2023)

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

A novel oleogel based on porous microgel from egg white - Buwei Liu; Lina Sun; Furong Jin; Yang Wan; Xiue Han; Tianxin Fu; Yongjia Guan; Zhixin Xie; Long Cheng; Bo Tian; Zhibiao Feng (Food Hydrocolloids, 2023)

The erythromycin sorption removal at environmentally relevant concentration based on molecular imprinted polymer: Performance and mechanism - Wen-Ming Xie; Yu Wu; Wan-Yang Yan; You Ma; Han Meng; Guo-Xiang Wang; Li-Min Zhang; Guo-Zheng Jia; Wei-Hua Li; Yan Xiao; Fang Fang (Environmental Pollution, 2023)

Janus membranes with simultaneous flux enhancement and fouling/wetting resistance prepared by a modified interfacial polymerization process for membrane distillation - Cheng Lei; Jinlong Han; Tengyu Cui; Weifeng Cao; Yinhua Wan; Haoli Zhou; Fei Shen (Desalination, 2023)

Adsorption of Li+ by imprinted capacitor deionization — A new method for selective recovery of valuable lithium in acidic solutions - Ning Han; Yifei Li; Haisen Peng; Ruize Gao; Qiongqiong He; Zhenyong Miao; Keji Wan (Desalination, 2023)

Nickel phosphide nanoarrays decorated on amorphous NiPOx/Fe(OH)3: A stable core–shell electrocatalyst for efficient oxygen evolution at large current density - Xinding Lv; Yan Li; Fei Deng; Haotong Li; Shutong Wan; Xue Han; Wanqi Zhang; Xia Tao (Chemical Engineering Journal, 2023)

Preparation of Yb–Sb co-doped Ti/SnO2 electrode for electrocatalytic degradation of sulfamethoxazole (SMX) - Xiao Han; Chenliang Zhou; Yongjing Chen; Yinhua Wan; Baozhi Zhang; Lili Shi; Shaoyuan Shi (Chemosphere, 2023)

Enhanced biological phosphorus removal by high concentration powder carrier bio-fluidized bed (HPB): Phosphorus distribution, cyclone separation, and metagenomics - Yanyu Mu; Li Wan; Zixuan Liang; Donghai Yang; Hongbo Han; Jing Yi; Xiaohu Dai (Chemosphere, 2023)

Energy management and balance strategy for underwater glider fleet with VMD-SSA-LSSVM model and central type double-level framework - Runfeng Zhang; Yanhui Wang; Xu Wan; Han Zhang; Shaoqiong Yang (Ocean Engineering, 2023)

Natural revegetation has dominated annual runoff reduction since the Grain for Green Program began in the Jing River Basin, Northwest China - Yipeng Yu; Pengtao Yu; Yanhui Wang; Yanfang Wan; Bin Wang; Xinsheng Han; Xinwu Tu; Jiamei Li; Lihong Xu; Xiao Wang; Zebin Liu (Journal of Hydrology, 2023)

A fully π-conjugated covalent organic framework with dual binding sites for ultrasensitive detection and removal of divalent heavy metal ions - Bin Zhu; Longyi Zhu; Shengyuan Deng; Ying Wan; Feng Qin; Haikang Han; Jun Luo (Journal of Hazardous Materials, 2023)

Molecular features, antioxidant potential, and immunological expression assessment of thioredoxin-like protein 1 (TXNL1) in yellowtail clownfish (Amphiprion clarkii) - M.A.H. Dilshan; W.K.M. Omeka; H.M.V. Udayantha; D.S. Liyanage; D.C.G. Rodrigo; H.A.C.R. Hanchapola; Y.K. Kodagoda; Jihun Lee; Sukkyoung Lee; Taehyug Jeong; Kyong Min Kim; Hyun-Ja Han; et al. (Fish & Shellfish Immunology, 2023)

Effect of adsorbate geometry and hydrogen bonding on the enhanced adsorption of VOCs by an interfacial Fe3O4–rGO heterostructure - Seongbin Lee; Sooyeon Kim; Sang Soo Han; Dong-Wan Kim; Jiwon Lee; Youngtak Oh (Chemical Engineering Journal, 2023)

CNIH4 governs cervical cancer progression through reducing ferroptosis - Jun-Yuan Yang; Dong Ke; Yanli Li; Jie Shi; Shi-Meng Wan; An-Jin Wang; Meng-Na Zhao; Han Gao (Chemico-Biological Interactions, 2023)

Two weeks dose range-finding and four weeks repeated dose oral toxicity study of a novel reversible monoamine oxidase B inhibitor KDS2010 in cynomolgus monkeys - Kyung-Tai Kim; Doo-Wan Cho; Jae-woo Cho; Wan-Jung Im; Da-Hee Kim; Jong-Hyun Park; Ki Duk Park; Young-Su Yang; Su-Cheol Han (Toxicological Research, 2023)

Modeling of breaching parameters for debris flow dams - He-chun Ruan; Hua-yong Chen; Xiao-qing Chen; Wan-yu Zhao; Jian-gang Chen; Tao Wang; Yao Jiang; Xi-an Wang; Xiang-ning Li; Xiao Li; Yun-han Yu (Journal of Mountain Science, 2023)

Molecular characterization, spatiotemporal expression patterns of fatty acid elongase (elovl8) gene, and its transcription changes in response to different diet stimuli in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Xiu-Ying Wei; Wei Qin; Chuan-Jie Qin; Qiong Shi; Sheng-Tao Guo; Panita Prathomya; Shi-Yong Zhang; Peng Fu; Wei Hu; Han-Wen Yuan; Zheng-Yong Wen (Frontiers in Marine Science, 2023)
Elongase of very long-chain fatty acid 8 (Elovl8) is a new member identified in the Elovl family that is involved in the synthesis of highly unsaturated fatty acids (HUFAs). However, the evolutionary and physiological roles of this enzyme are still largely unknown. In the present study, the elovl8 gene was identified and characterized from yellow catfish Pelteobagrus fulvidraco , and then its evolutionary and molecular characteristics as well as transcriptional changes in response to various nutritional status were determined. Results showed that the open reading frame (ORF) of elovl8 was 795 bp in length, encoding a protein of 264 amino acids. Multiple sequences alignment showed that the yellow catfish Elovl8 was highly conserved with other homologs in teleosts, sharing similar structural characteristics (including six conserved transmembrane α-helical domains, four conserved elongase motifs, and three highly conserved cysteine residues). Meanwhile, comparisons of genetic synteny confirmed that the elovl8 gene identified from the yellow catfish was the homolog of elovl8b in other teleosts, and thus, the elovl8a gene was lost in the genome of the yellow catfish. Gene structure analysis revealed that the elovl8b gene contained eight exons and seven introns, which was highly conserved in teleosts, implying the functional conservation among various fish species. Tissue distribution analysis detected by real-time quantitative PCR (RT-qPCR) showed that the elovl8 gene was extensively expressed in all detected tissues except eyes, with high expression levels in the intestine and liver. Temporal expression analysis revealed that the expression level of elovl8 was stably expressed in the early 12 h after fertilization, and then dramatically decreased at 24, 48, 72, and 96 h after fertilization, implying that elovl8 is required for HUFA biosynthesis in the early development stages. Functional experiments showed that the expression of the elovl8 gene was stimulated after feeding with egg yolk but was not obviously affected after feeding with halogenated worms, indicating that diets full of HUFAs can inhibit the expression of elovl8 in yellow catfish. Our findings will help us to better understand the evolutionary and functional characteristics of elovl8 in teleosts, and lay a solid basis for investigating the regulation mechanism of HUFA biosynthesis.

Soil physiochemical properties and bacterial community changes under long-term polycyclic aromatic hydrocarbon stress in situ steel plant soils - Liuqing Yang; Dongfei Han; Decai Jin; Jingran Zhang; Yongping Shan; Mengxue Wan; Yongfei Hu; Wentao Jiao (Chemosphere, 2023)

Efficient removal of electroneutral carbonyls by combined vacuum–UV oxidation and anion-exchange resin adsorption: mechanism, model simulation, and optimization - Han-Ying Cai; Qian-Yuan Wu; Wan-Yue Ouyang; Hong-Ying Hu; Wen-Long Wang (Water Research, 2023)

Characteristics of persulfate gel materials in groundwater remediation: Column and tank experiments investigations - Yu Yang; Xiangjian Xu; Fu Xia; Shuoyang Wan; Xu Han; Han Xiao; Sheng Deng; Yonghai Jiang; Xiang Li (Science of The Total Environment, 2023)

In situ generated of hybrid interface in poly(1,3-dioxolane) quasi solid electrolyte and extended sulfone cosolvent for lithium-metal batteries - Bo-Han Zhang; Wan-Xin Wen; Hua-Ying Wang; Yun-Lei Hou; Jing-Zhou Chen; Dong-Lin Zhao (Chemical Engineering Journal, 2023)

Applicability of core-shell SiO2 microspheres with a high TiO2 loading as stationary phase for HPLC - Dian Wang; Xiang Wan; Jiafei Wang; Debby Mangelings; Qin Xu; Fazhi Xie; Xianhuai Huang; Weihua Li; Han Xuan; Wensheng Zou; Qishu Qu (Analytica Chimica Acta, 2023)

Preclinical evaluation of general toxicity and safety pharmacology of a receptor-binding domain-based COVID-19 subunit vaccine in various animal models - Sang-Jin Park; Min Seong Jang; Kwang-Hyun Lim; Joung‐Wook Seo; Wan-Jung Im; Kang-Hyun Han; Seong-Eun Kim; Eunhee Jang; Danbi Park; Yong-Bum Kim (Archives of Toxicology, 2023)

Deciphering the roles of aryl hydrocarbon receptor (AHR) in regulating carcinogenesis - Zhi Xiong Chong; Chean Yeah Yong; Alan Han Kiat Ong; Swee Keong Yeap; Wan Yong Ho (Toxicology, 2023)

Sediment records of black carbon variations over the last two centuries in North China - Dejun Wan; Yongming Han; Lei Song; Dongliang Ning; Qingfeng Jiang (Science of The Total Environment, 2023)

Changes in soil free-living diazotrophic community and co-occurrence patterns along desert wetland degradation gradient in the Mu Us Desert, northern China - Kun WANG; Hongyan FEI; Qian TONG; Chuanyu WAN; Ruopeng PAN; Fengpeng HAN (Pedosphere, 2023)

Depletion attraction driven formation of Spirulina emulsion gels for 3D printing - Guangxin Feng; Gaoshang Wang; Qing Li; Chuanwu Han; Dong Wei; Jian Guo; Zhili Wan; Jinmei Wang; Xiaoquan Yang (Food Hydrocolloids, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Metal–support interface engineering of Ni catalysts for improved H2 storage performance: Grafting alkyltriethoxysilane onto commercial alumina - Hwi Ju Jung; Hwiram Jeong; Dongun Kim; Hyerim Ko; Gi Bo Han; Byunghun Jeong; Tae Wan Kim; Young-Woong Suh (Chemical Engineering Journal, 2023)

Repetitive transcranial magnetic stimulation alleviates glial activation through suppressing HMGB1/TLR4 pathway in a rat model of Parkinson’s disease - Chao Han; Xue Zhang; Kaixin Dou; Weichao Yao; Minyi Yao; Qi Wan; Anmu Xie (Molecular Biology Reports, 2023)
Background Repetitive transcranial magnetic stimulation (rTMS) has been demonstrated to be effective in Parkinson’s disease (PD), but whether rTMS treatment has a relieving effect on neuroinflammation remains to be investigated. In this article, we explored the effects of rTMS on forelimb use asymmetry and neuroinflammation-related mechanisms in a 6-hydroxydopamine (6-OHDA)-induced PD rat model. Methods and results Rats in the 6-OHDA+rTMS group received 10 Hz rTMS daily for 4 weeks. Behavioral tests (the cylinder test) were performed at the 3rd and 7th weeks after the operation. Astrocyte and microglia activation and protein levels of tyrosine hydroxylase(TH), high-mobility group box 1(HMGB1) and toll-like receptors 4(TLR4) were investigated by immunohistochemistry and Western blot analyses, respectively. After 4 weeks of treatment, forelimb use asymmetry was ameliorated in the 6-OHDA+rTMS group. Consistent with the behavioral tests, rTMS increased TH in the substantia nigra (SN) and the striatum of PD rats. High glial activation and HMGB1/TLR4 expression in the SN and the striatum were observed in the 6-OHDA group, while rTMS alleviated these changes. Conclusions This study showed that rTMS might be a promising method for alleviating neuroinflammation in PD rat models, and the effects might be mediated through the downregulation of the HMGB1/TLR4 pathway.

Baicalein sensitizes triple negative breast cancer MDA-MB-231 cells to doxorubicin via autophagy-mediated down-regulation of CDK1 - Fang Hua; Yi-Yi Xiao; Xin-Hui Qu; Shan-Shan Li; Kun Zhang; Chao Zhou; Jian-Le He; Ye Zhu; Yu-Ying Wan; Li-Ping Jiang; Fang-Fang Tou; Xiao-Jian Han (Molecular and Cellular Biochemistry, 2023)

Volunteering in nature: a win–win strategy for healthy people and healthy nature - Wan-Yu Chou; Shih-Han Hung; Chun-Yen Chang; Tsu-Liang Chang (Landscape and Ecological Engineering, 2023)

Gas production characteristics of biogenic gas simulated in hydrate-developing area of Dongsha area, South China Sea - Pibo Su; Wei Wei; Chaoqi Shi; Jin Li; Weifeng Han; Zebang Xiao; Jinqiang Liang; Feifei Wang; Zhifeng Wan (Frontiers in Marine Science, 2023)
Most of the natural gas hydrate sources in the world are biogenic gas, but there are still many unsolved problems in the formation process of biogenic gas. The gas source of gas hydrates in the northern South China Sea is also controversial, and the evaluation of biogas source rock in hydrate development areas lacks experimental basis and quantitative data. In order to solve these problems, this paper used the sediments obtained from the GMGS2 hydrate drilling voyage to simulate the biological gas production. Through the culture experiment, the relationship between sedimentary gas production, temperature and sediment characteristics in the hydrate development area of Dongsha Sea area was comparatively studied, and the results were compared with typical biological gas fields. The results showed that CH 4 and CO 2 were the main gas products, and a small amount of H 2 was formed. Methane yield is closely related to temperature, and the optimal temperature range in the study area is 20°C~ 40°C. At the same time, it is found that organic carbon content (TOC) has no significant correlation with methane yield, and it is not suitable to be used as an index for the evaluation of biogas source rock. Comprehensive analysis shows that the methane production rate in the study area is relatively high and the hydrocarbon generation potential is great, which meets the gas source conditions for the formation of gas hydrate ore body. The main factors affecting biomethane yield include available organic matter, bacterial community and environmental factors.

Bacterial community mapping of the AIA mouse gastrointestinal tract under dietary intervention with skipjack tuna (Katsuwonus pelamis) elastin peptides - Qiaoli Wu; Bing Liu; Rongxian Yu; Xiaoling Sun; Ziyan Wang; Jun Zhou; Chenyang Lu; Haitao Wan; Jing Zhang; Jiaojiao Han; Xiurong Su (Food Bioscience, 2023)

Effects of thermal processing on transformation of polyphenols and flavor quality - Zongde Jiang; Zisheng Han; Mengting Zhu; Xiaochun Wan; Liang Zhang (Current Opinion in Food Science, 2023)

Direct 4D printing of gradient structure of ceramics - Lei Wan; Zhengyi Mao; Hui Liu; Youneng Xie; Fucong Lyu; Zhaowenbo Cao; Yunhu He; Jianan Yin; Xiongqi Han; Wai Yan Kannie Chan; Jian Lu (Chemical Engineering Journal, 2023)

Enhanced in-situ sludge reduction of the side-stream process via employing micro-aerobic approach in both mainstream and side-stream - Si-Mai Peng; Hai-Chao Luo; Zi-Han Wang; Shan-Shan Yang; Wan-Qian Guo; Nan-Qi Ren (Bioresource Technology, 2023)

Structure and Evolution of Clay-Organic Nanocomposites in Three Leading Shales in China - Yuantao Gu; Quan Wan; Xiaoxia Li; Tao Han; Shuguang Yang; Qinhong Hu (Journal of Earth Science, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Mammalian carcass decay increases carbon storage and temporal turnover of carbon-fixing microbes in alpine meadow soil - Xiaochen Wang; Qian Han; Qiaoling Yu; Sijie Wang; Jiawei Yang; Wanghong Su; Ruijun Wan-Yan; Xiaofang Sun; Huan Li (Environmental Research, 2023)

Seasonal changes in diurnal rainfall over Sri Lanka and possible mechanisms - Wan-Ru Huang; Suranjith Bandara Koralegedara; Po-Han Tung; Tzu-Yang Chiang (Atmospheric Research, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

Transcriptomics analysis of mangosteen ripening revealed active regulation of ethylene, anthocyanin and xanthone biosynthetic genes - Ili Nadhirah Jamil; Azhani Abdul-Rahman; Hoe-Han Goh; Wan Mohd Aizat (Postharvest Biology and Technology, 2023)

Effects of pre-emulsified safflower oil with magnetic field modified soy 11S globulin on the gel, rheological, and sensory properties of reduced-animal fat pork batter - Zhuang-Li Kang; Jing-jie Xie; Yan-ping Li; Wan-jie Song; Han-Jun Ma (Meat Science, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Heavy metal contamination and risk assessment in winter jujube (Ziziphus jujuba Mill. cv. Dongzao) - Min Xu; Qiusheng Chen; Xiabing Kong; Lingxi Han; Qiang Zhang; Qingjun Li; Bianqing Hao; Xubo Zhao; Lu Liu; Haoliang Wan; Jiyun Nie (Food and Chemical Toxicology, 2023)

Barium titanate@covalent organic framework core–shell nanoparticles for adsorption-enhanced piezo-photocatalysis - Licheng Wan; Jun Han; Wenrou Tian; Najun Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Removal of nitrate nitrogen from wastewater by green synthetic hydrophilic activated carbon supported sulfide modified nanoscale zerovalent Iron: Characterization, performance and mechanism - Shuaibing Fang; Jingxi Zhang; Yifan Niu; Shaohua Ju; Yongwan Gu; Kai Han; Xiaoxi Wan; Na Li; Yu Zhou (Chemical Engineering Journal, 2023)

Assessment of the orbital variations of GNSS GEO and IGSO satellites for monitoring ionospheric TEC - Zhiyao Li; Jiahao Zhong; Yongqiang Hao; Meng Zhang; Jiemin Niu; Xin Wan; Fuqing Huang; Hao Han; Xingyan Song; Jiawen Chen (GPS Solutions, 2023)

Co-pyrolysis technology for enhancing the functionality of sewage sludge biochar and immobilizing heavy metals - Zeyu Fan; Xian Zhou; Ziling Peng; Sha Wan; Zhuo Fan Gao; Shanshan Deng; Luling Tong; Wei Han; Xia Chen (Chemosphere, 2023)

Identification and characterization of two transcriptional regulators in Xanthomonas oryzae pv. oryzicola YM15 - Xiaoyan Wan; Waqar Ahmed; Jun Yang; Han Meng; Lanfang Wei; Guanghai Ji (Physiological and Molecular Plant Pathology, 2023)

Visualization and metabolome for the migration and distribution behavior of pesticides residue in after-ripening of banana - Meiran Wang; Qiaoxia Tian; Hongxing Li; Longjun Dai; Yi Wan; Mingyue Wang; Bingjun Han; Huaping Huang; Yunuo Zhang; Juncheng Chen (Journal of Hazardous Materials, 2023)

Transcriptomic analysis of polyketide synthesis in dinoflagellate, Prorocentrum lima - Xiukun Wan; Ge Yao; Kang Wang; Shaoheng Bao; Penggang Han; Fuli Wang; Tianyu Song; Hui Jiang (Harmful Algae, 2023)

Soil microbial necromass: The state-of-the-art, knowledge gaps, and future perspectives - Hanqing Wu; Sichen Wan; Chujin Ruan; Wei Wan; Miao Han; Guowei Chen; Ying Liu; Kun Zhu; Chao Liang; Gang Wang (European Journal of Soil Biology, 2023)

Impact of biochar amendment on antibiotic removal and ARGs accumulation in constructed wetlands for low C/N wastewater treatment - Fidelis Odedishemi Ajibade; Wan-Xin Yin; Awoke Guadie; Temitope Fausat Ajibade; Ying Liu; Mathieu Nsenga Kumwimba; Wen-Zong Liu; Jing-Long Han; Hong-Cheng Wang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Soil microbial community is resilient to thinning disturbance - Wan-Rou Lin; Wen-Cheng Chen; Pi-Han Wang (Tropical Ecology, 2023)

Trim28 citrullination maintains mouse embryonic stem cell pluripotency via regulating Nanog and Klf4 transcription - Yaguang Zhang; Xiaowen Wan; Lei Qiu; Lian Zhou; Qing Huang; Mingtian Wei; Xueqin Liu; Sicheng Liu; Bo Zhang; Junhong Han (Science China Life Sciences, 2023)

Classifying Temporomandibular Disorder with Artificial Intelligent Architecture Using Magnetic Resonance Imaging - Zih-Kai Kao; Neng-Tai Chiu; Hung-Ta Hondar Wu; Wan-Chen Chang; Ding-Han Wang; Yen-Ying Kung; Pei-Chi Tu; Wen-Liang Lo; Yu-Te Wu (Annals of Biomedical Engineering, 2023)

Novel economy and carbon emissions prediction model of different countries or regions in the world for energy optimization using improved residual neural network - Yongming Han; Lian Cao; Zhiqiang Geng; Weiying Ping; Xiaoyu Zuo; Jinzhen Fan; Jing Wan; Gang Lu (Science of The Total Environment, 2023)

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

Microplastics reduce nitrogen uptake in peanut plants by damaging root cells and impairing soil nitrogen cycling - Yiyang Liu; Fangji Xu; Liping Ding; Guanchu Zhang; Bo Bai; Yan Han; Lina Xiao; Yan Song; Ying Li; Shubo Wan; Guowei Li (Journal of Hazardous Materials, 2023)

A review on lignin waste valorization by catalytic pyrolysis: Catalyst, reaction system, and industrial symbiosis mode - Shaoqing Wang; Zhen Wan; Yu Han; Yan Jiao; Zhihe Li; Peng Fu; Ning Li; Andong Zhang; Weiming Yi (Journal of Environmental Chemical Engineering, 2023)

Mechanosensitive Ion Channel TMEM63A Gangs Up with Local Macrophages to Modulate Chronic Post-amputation Pain - Shaofeng Pu; Yiyang Wu; Fang Tong; Wan-Jie Du; Shuai Liu; Huan Yang; Chen Zhang; Bin Zhou; Ziyue Chen; Xiaomeng Zhou; Qingjian Han; Dongping Du (Neuroscience Bulletin, 2023)
Post-amputation pain causes great suffering to amputees, but still no effective drugs are available due to its elusive mechanisms. Our previous clinical studies found that surgical removal or radiofrequency treatment of the neuroma at the axotomized nerve stump effectively relieves the phantom pain afflicting patients after amputation. This indicated an essential role of the residual nerve stump in the formation of chronic post-amputation pain (CPAP). However, the molecular mechanism by which the residual nerve stump or neuroma is involved and regulates CPAP is still a mystery. In this study, we found that nociceptors expressed the mechanosensitive ion channel TMEM63A and macrophages infiltrated into the dorsal root ganglion (DRG) neurons worked synergistically to promote CPAP. Histology and qRT-PCR showed that TMEM63A was mainly expressed in mechanical pain-producing non-peptidergic nociceptors in the DRG, and the expression of TMEM63A increased significantly both in the neuroma from amputated patients and the DRG in a mouse model of tibial nerve transfer (TNT). Behavioral tests showed that the mechanical, heat, and cold sensitivity were not affected in the Tmem63a -/- mice in the naïve state, suggesting the basal pain was not affected. In the inflammatory and post-amputation state, the mechanical allodynia but not the heat hyperalgesia or cold allodynia was significantly decreased in Tmem63a -/- mice. Further study showed that there was severe neuronal injury and macrophage infiltration in the DRG, tibial nerve, residual stump, and the neuroma-like structure of the TNT mouse model, Consistent with this, expression of the pro-inflammatory cytokines TNF-α, IL-6, and IL-1β all increased dramatically in the DRG. Interestingly, the deletion of Tmem63a significantly reduced the macrophage infiltration in the DRG but not in the tibial nerve stump. Furthermore, the ablation of macrophages significantly reduced both the expression of Tmem63a and the mechanical allodynia in the TNT mouse model, indicating an interaction between nociceptors and macrophages, and that these two factors gang up together to regulate the formation of CPAP. This provides a new insight into the mechanisms underlying CPAP and potential drug targets its treatment.

Sustained power output from an algal biophotovoltaic (BPV) platform using selected marine and freshwater microalgae - Cheng-Han Thong; Fong-Lee Ng; Vengadesh Periasamy; Wan Jeffrey Basirun; G. Gnana Kumar; Siew-Moi Phang (Journal of Applied Phycology, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

VUV/UV oxidation performance for the elimination of recalcitrant aldehydes in water and its variation along the light-path - Wan-Yue Ouyang; Wen-Long Wang; Yi-Lin Zhang; Han-Ying Cai; Qian-Yuan Wu (Water Research, 2023)

Seasonal variation and ecological risk assessment of Pharmaceuticals and Personal Care Products (PPCPs) in a typical semi-enclosed bay — The Bohai Bay in northern China - Kun Lin; Rui Wang; Tongzhu Han; Liju Tan; Xue Yang; Mengmeng Wan; Yanshan Chen; Ting Zhao; Shan Jiang; Jiangtao Wang (Science of The Total Environment, 2023)

Sex-specific associations between legacy and novel per- and polyfluoroalkyl substances and telomere length in newborns in Wuhan, China: Mixture and single pollutant associations - Xiaojun Li; Hongxiu Liu; Hongxia Wan; Yuanyuan Li; Shunqing Xu; Han Xiao; Wei Xia (Science of The Total Environment, 2023)

Impacts of land uses on spatio-temporal variations of seasonal water quality in a regulated river basin, Huai River, China - Lingqing Wang; Xiaoxiao Han; Yongyong Zhang; Qian Zhang; Xiaoming Wan; Tao Liang; Hocheol Song; Nanthi Bolan; Sabry M. Shaheen; John R. White; Jörg Rinklebe (Science of The Total Environment, 2023)

Residue analysis and effect of preharvest forchlorfenuron (CPPU) application on quality formation of kiwifruit - Haoliang Wan; Xiabing Kong; Yihui Liu; Fen Jin; Lingxi Han; Min Xu; Xiaoming Li; Li Li; Jun Yang; Dengni Lai; Jiyun Nie (Postharvest Biology and Technology, 2023)

Environmentally friendly, non-glove box, closed-system and continuously massive production of lithium sulfide for battery applications - Shunjin Yang; Fengming Wan; Aiguo Han; Liran Fang; Qifang Sun; Zixiang Zhao; Dawei Song; Lianqi Zhang; Lifang Chen; Colin A. Wolden; Xin Zhang; Yongan Yang (Journal of Cleaner Production, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Rapid preparation of nickel fluoride motif via solution-free plasma route for high-energy aqueous hybrid supercapacitor - Nilesh R. Chodankar; Indrajit V. Bagal; Swati J. Patil; Seung-Kyu Hwang; Pragati A. Shinde; Amar M. Patil; Smita V. Karekar; Amal Al Ghaferi; Wenli Zhang; Sang-Wan Ryu; Yun Suk Huh; Young Kyu Han (Chemical Engineering Journal, 2023)

A symbiosis between Euploea butterflies and yeasts - Wan-Rou Lin; Yi-Ping Chang; Hui-Lin Wu; I-Cheng Hsu; Pi-Han Wang (Symbiosis, 2023)

Assimilation of Ocean Surface Wind Data by the HY-2B Satellite in GRAPES: Impacts on Analyses and Forecasts - Jincheng Wang; Xingwei Jiang; Xueshun Shen; Youguang Zhang; Xiaomin Wan; Wei Han; Dan Wang (Advances in Atmospheric Sciences, 2023)

Autoregressive count data modeling on mobility patterns to predict cases of COVID-19 infection - Jing Zhao; Mengjie Han; Zhenwu Wang; Benting Wan (Stochastic Environmental Research and Risk Assessment, 2022)
At the beginning of 2022 the global daily count of new cases of COVID-19 exceeded 3.2 million, a tripling of the historical peak value reported between the initial outbreak of the pandemic and the end of 2021. Aerosol transmission through interpersonal contact is the main cause of the disease’s spread, although control measures have been put in place to reduce contact opportunities. Mobility pattern is a basic mechanism for understanding how people gather at a location and how long they stay there. Due to the inherent dependencies in disease transmission, models for associating mobility data with confirmed cases need to be individually designed for different regions and time periods. In this paper, we propose an autoregressive count data model under the framework of a generalized linear model to illustrate a process of model specification and selection. By evaluating a 14-day-ahead prediction from Sweden, the results showed that for a dense population region, using mobility data with a lag of 8 days is the most reliable way of predicting the number of confirmed cases in relative numbers at a high coverage rate. It is sufficient for both of the autoregressive terms, studied variable and conditional expectation, to take one day back. For sparsely populated regions, a lag of 10 days produced the lowest error in absolute value for the predictions, where weekly periodicity on the studied variable is recommended for use. Interventions were further included to identify the most relevant mobility categories. Statistical features were also presented to verify the model assumptions.

RETRACTED ARTICLE: Long non-coding RNA H19X promotes tumorigenesis and metastasis of colorectal cancer through regulating the miR-503-5p/KANK1 axis - Zihan Yuan; Haizhou Zhao; Qiaoming Zhi; Sentai Wang; Chao Liu; Ye Han; Zhihua Xu; Fei Liu; Xingyi Liu; Xinquan Zan; Qiang Wang; Daiwei Wan (Genes & Genomics, 2022)

Effects of ridge planting on crop seedlings under saline water drip irrigation - Xiaoyu Han; Yaohu Kang; Shuqin Wan; Dan Li (Irrigation and Drainage, 2022)
A field experiment was conducted in northwest China to study the effects of different irrigation water salinity levels on the emergence and growth of corn, sunflower, summer squash, and cowpea. Two tillage systems (flat and ridge planting) and five salinity levels (at 1.7, 4.0, 6.3, 8.6, and 10.9 dS/m) were tested. Compared with flat planting, the soil salinity within 30 cm horizontally from the drip tapes decreased by 15% in the ridge planting system. Ridge planting significantly improved the emergence and growth of crops, which was mainly manifested in higher emergence rates, reduced emergence time, and increased dry biomass, especially under high‐salinity conditions (electrical conductivity of irrigation water >4 dS/m). The electrolytic conductivity of the saturation extract threshold at which corn, sunflower, summer squash, and cowpea endured without reduced emergence rates was 5.8, 5.8, 4.8, and 4.0 dS/m, respectively. Above this threshold, the relative emergence rate decreased by 11%, 16%, 14%, and 20%, respectively. Our results indicate the agronomic benefits of ridge planting, and the soil environment was improved by ridge planting with saline water drip irrigation. In addition, we discuss the crop responses in terms of emergence rates and relative seedling dry biomass in relation to soil salinity. Suggestions for the secure and efficient use of saline water for irrigation in arid regions have been put forward.

New taxonomic framework for Arthrodermataceae: a comprehensive analysis based on their phylogenetic reconstruction, divergence time estimation, phylogenetic split network, and phylogeography - Zhi-Yuan Zhang; Yu-Lian Ren; Xin Li; Wan-Hao Chen; Jian-Dong Liang; Yan-Feng Han; Zong-Qi Liang (Antonie van Leeuwenhoek, 2022)

Broussonetia × hanjiana (Moraceae) microsatellite markers for species and ploidy determination developed using next-generation sequencing - Hyo-In Lim; Ji-Young Ahn; Han-Na Seo; Seung-Beom Chae; Jei-Wan Lee (Molecular Biology Reports, 2022)

The Rhizosphere Microbial Index Reflects the Optimal Restoration Pattern and the Nutrient Preference of Rhizosphere Microbes of Typical Plants in a Desertified Environment - Boyuan Bi; Chuanyu Wan; Qian Tong; Kun Wang; He Zhang; Yu Wang; Fengpeng Han (Journal of Soil Science and Plant Nutrition, 2022)

Lithology identification method based on integrated K-means clustering and meta-object representation - Zhimin Cao; Can Yang; Jian Han; Haiwei Mu; Chuan Wan; Pan Gao (Arabian Journal of Geosciences, 2022)

Rainstorm-induced large-scale landslides in Northeastern Chongqing, China, August 31 to September 2, 2014 - Bin Li; Yang Gao; Yueping Yin; Jiawei Wan; Kai He; Weile Wu; Han Zhang (Bulletin of Engineering Geology and the Environment, 2022)

Bacterial Metabolic Response to Change in Phytoplankton Communities and Resultant Effects on Carbon Cycles in the Amundsen Sea Polynya, Antarctica - Bomina Kim; Sung-Han Kim; Jun-Oh Min; Youngju Lee; Jinyoung Jung; Tae-Wan Kim; Jae Seong Lee; Eun Jin Yang; Jisoo Park; SangHoon Lee; Jung-Ho Hyun (Frontiers in Marine Science, 2022)
We investigated changes in heterotrophic bacterial metabolic activities and associated carbon cycles in response to a change in dominant phytoplankton communities during two contrasting environmental conditions in austral summer in the Amundsen Sea polynya (ASP), Antarctica: the closed polynya condition in 2014 (ANA04) and the open polynya condition in 2016 (ANA06). In ANA04, Phaeocystis antarctica predominated phytoplankton biomass, comprising 78% of total phytoplankton carbon biomass, whereas diatoms and Dictyocha speculum accounted for 45% and 48% of total phytoplankton carbon biomass, respectively, in ANA06. Bacterial production (BP) showed a significant positive correlation with only chlorophyll-a (Chl-a, rho = 0.66, p < 0.001) in P. antarctica -dominated ANA04, whereas there were significant positive relationships of BP with various organic carbon pools, such as chromophoric dissolved organic matter (CDOM, rho = 0.84, p < 0.001), Chl-a (rho = 0.59, p < 0.001), and dissolved organic carbon (DOC, rho = 0.51, p = 0.001), in ANA06 when diatoms and D. speculum co-dominated. These results indicate that BP depended more on DOC directly released from P. antarctica in ANA04, but was supported by DOC derived from various food web processes in the diatom-dominated system in ANA06. The BP to primary production (BP : PP) ratio was three-fold higher in P. antarctica -dominated ANA04 (BP: PP = 0.09), than in diatom- and D. speculum -co-dominated ANA06 (BP : PP = 0.03). These results suggested that the microbial loop is more significant in Phaeocystis -dominated conditions than in diatom-dominated conditions. In addition, the decreases in BP : PP ratio and bacterial respiration with increasing diatom proportion in the surface mixed layer indicated that the change from P. antarctica to diatom predominance enhanced biological carbon pump function by increasing particulate organic carbon export efficiency. Consequently, our results suggest that bacterial metabolic response to shifts in phytoplankton communities could ultimately affect larger-scale ecological and biogeochemical processes in the water column of the ASP.

Whole Genome Sequencing and Biological Characteristics of Two Strains of Porcine Escherichia coli Isolated from Saba Pigs - Bo Zhang; Weiwei Zhao; Bin Gao; Chunlan Shan; Xi Wang; Quan Wan; Jing Deng; Jinglong Cha; Bingxun Chen; Dongmei Han; Libo Gao; Pingxing Ao; et al. (Current Microbiology, 2022)

Association between UBAC2 gene polymorphism and the risk of noise-induced hearing loss: a cross-sectional study - Liu Wan; Ludi Zhang; Peng Sun; Lei Han; Hengdong Zhang; Baoli Zhu; Boshen Wang (Environmental Science and Pollution Research, 2022)

Sympathetic Nerve Mediated Spinal Glia Activation Underlies Itch in a Cutaneous T-Cell Lymphoma Model - Fang Tong; Qianru He; Wan-Jie Du; Huan Yang; Dongping Du; Shaofeng Pu; Qingjian Han (Neuroscience Bulletin, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Correction to: Feature selection and risk prediction for patients with coronary artery disease using data mining - Nashreen Md Idris; Yin Kia Chiam; Kasturi Dewi Varathan; Wan Azman Wan Ahmad; Kok Han Chee; Yih Miin Liew (Medical & Biological Engineering & Computing, 2022)

Spatiotemporal distribution and the passive dispersal of fungal spores through HVAC systems - Wan-Rou Lin; Yung-Hung Ho; Wai Kwan Lee; Hsuan-Min Cheng; Pi-Han Wang (Aerobiologia, 2022)

Cancerous Inhibitor of Protein Phosphatase 2A (CIP2A): Could It Be a Promising Biomarker and Therapeutic Target in Parkinson’s Disease? - Sijia Yin; Chao Han; Yun Xia; Fang Wan; Junjie Hu; Liang Kou; Yadi Sun; Jiawei Wu; Yunna Li; Qiulu Zhou; Nian Xiong; Jinsha Huang; et al. (Molecular Neurobiology, 2022)
Parkinson’s disease (PD) is an incurable neurodegenerative disease characterized by aggregation of pathological alpha-synuclein (α-syn) and loss of dopaminergic neuron in the substantia nigra. Inhibition of phosphorylation of the α-syn has been shown to mediate alleviation of PD-related pathology. Protein phosphatase 2A (PP2A), an important serine/threonine phosphatase, plays an essential role in catalyzing dephosphorylation of the α-syn. Here, we identified and validated cancerous inhibitor of PP2A (CIP2A), as a potential diagnostic biomarker for PD. Our data showed that plasma CIP2A concentrations in PD patients were significantly lower compared to age- and sex-matched controls, 1.721 (1.435–2.428) ng/ml vs 3.051(2.36–5.475) ng/ml, p < 0.0001. The area under the curve of the plasma CIP2A in distinguishing PD from the age- and sex-matched controls was 0.776. In addition, we evaluated the role of CIP2A in PD-related pathogenesis in PD cellular and MPTP-induced mouse model. The results demonstrated that CIP2A is upregulated in PD cellular and MPTP-induced mouse models. Besides, suppression of the CIP2A expression alleviates rotenone induced aggregation of the α-syn as well as phosphorylation of the α-syn in SH-SY5Y cells, which is associated with increased PP2A activity. Taken together, our data demonstrated that CIP2A plays an essential role in the mechanisms related to PD development and might be a novel PD biomarker.

Circ-TFF1 Facilitates Breast Cancer Development via Regulation of miR-338-3p/FGFR1 Axis - Long Wan; Qi Han; Bisheng Zhu; Zhihua Kong; Enrong Feng (Biochemical Genetics, 2022)

Application of mathematical functions for seismic increment fragility determination - Junwon Seo; Alan James Hatlestad; Jung-Han Kimn; Jong Wan Hu (European Journal of Environmental and Civil Engineering, 2022)

Integrated pest management of Tuta absoluta: practical implementations across different world regions - Nicolas Desneux; Peng Han; Ramzi Mansour; Judit Arnó; Thierry Brévault; Mateus R. Campos; Anais Chailleux; Raul N. C. Guedes; Javad Karimi; Kouassi Arthur J. Konan; Anne-violette Lavoir; María G. Luna; et al. (Journal of Pest Science, 2022)

SDF-1 secreted by mesenchymal stem cells promotes the migration of endothelial progenitor cells via CXCR4/PI3K/AKT pathway - Xiaoyi Wang; Huijiao Jiang; Lijiao Guo; Sibo Wang; Wenzhe Cheng; Longfei Wan; Zhongzhou Zhang; Lihang Xing; Qing Zhou; Xiongfeng Yang; Huanhuan Han; Xueling Chen; et al. (Journal of Molecular Histology, 2021)

Exposure to 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol and risk of thyroid cancer: a case-control study in China - Wan-Jun Yang; Hua-Bing Wu; Chi Zhang; Qi Zhong; Ming-Jun Hu; Jia-Liu He; Guo-Ao Li; Zhen-Yu Zhu; Jin-Liang Zhu; Huan-Huan Zhao; Han-Shuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Shifts in Nitrogen Removal Performance and Microbial Communities in Constructed Wetlands After Short-term Exposure to Titanium Dioxide Nanoparticles - Rui Han; Kexin Li; Chenzheng We; Tao He; Jingru Liu; Renduo Zhang; Li Wan; Yinghai Wu (Water, Air, & Soil Pollution, 2021)

Genetic mapping reveals BjRf as a candidate gene controlling fertility restoration of the oxa CMS in Brassica juncea - Qiqi Cheng; Peijie Yao; Hui Li; Yiming Han; Kejing Xu; Shuangping Heng; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2021)

Folate metabolizing gene polymorphisms and genetic vulnerability to preterm birth in Korean women - Bit Na Kwon; Noo Ri Lee; Hyung Jun Kim; Yun Dan Kang; Jong Soo Kim; Jin Wan Park; Han Jun Jin (Genes & Genomics, 2021)

Surface charge engineering of Thermomyces lanuginosus lipase improves enzymatic activity and biodiesel synthesis - Nanyu Han; Minyuan Tang; Sidi Wan; Zhanbao Jiang; Yong Yue; Xiangui Zhao; Jinrun Yang; Zunxi Huang (Biotechnology Letters, 2021)

Inactivation of the β (1, 2)-xylosyltransferase and the α (1, 3)-fucosyltransferase gene in rice (Oryza sativa) by multiplex CRISPR/Cas9 strategy - Jae-Wan Jung; Jun-Hye Shin; Won-Kyung Lee; Hilal Begum; Chan-Hong Min; Mi-Hwa Jang; Han-Bin Oh; Moon-Sik Yang; Seong-Ryong Kim (Plant Cell Reports, 2021)

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

Global soil microbial biomass decreases with aridity and land‐use intensification - Xiaohua Wan; Xinli Chen; Zhiqun Huang; Han Y. H. Chen (Global Ecology and Biogeography, 2021)
Aim Although global patterns are emerging for the soil total microbial biomass pool, our understanding of the distribution of the finer groups, especially bacterial and fungal biomass, remains limited. Moreover, we lack mechanistic insights into the global variation of soil microbial biomass. Location Global terrestrial ecosystems. Time period 1990–2019. Major taxa studied Bacteria and fungi. Methods By conducting a global synthesis of 4,472 observations from 577 sites published in 404 studies, we examined the global patterns and drivers of the soil total microbial biomass, bacterial and fungal biomass and fungi‐to‐bacteria ratio. Results We found that soil total microbial, bacterial and fungal biomass peaked concurrently in tundras, with lower values in deserts, and that intensification of land use reduced soil total microbial, bacterial and fungal biomass and the fungi‐to‐bacteria biomass ratio. Soil organic carbon was the most important driver for global distribution patterns of both bacterial and fungal biomass. Our structural equation models indicated that soil bacterial and fungal biomass increased with water availability through its positive effect on soil organic carbon on a global scale. In contrast, soil total, bacterial and fungal biomass decreased with mean annual temperature and intensification of land use via their negative effects on soil organic carbon. Main conclusions Our results suggest that decreasing water availability and land‐use intensification could reduce soil microbial biomass and the relative abundance of soil fungi to bacteria, impairing their functions and the services they provide.

The youngest matrix of 234 Ma of the Kanguer accretionary mélange containing blocks of N-MORB basalts: constraints on the northward subduction of the Paleo-Asian Kanguer Ocean in the Eastern Tianshan of the Southern Altaids - Songjian Ao; Qigui Mao; Brian F. Windley; Dongfang Song; Zhiyong Zhang; Ji’en Zhang; Bo Wan; Chunming Han; Wenjiao Xiao (International Journal of Earth Sciences, 2021)

Hydrochemical appraisal of groundwater quality and pollution source analysis of oil field area: a case study in Daqing City, China - Han Zhang; Jianmin Bian; Hanli Wan (Environmental Science and Pollution Research, 2021)

Molecular characterization of a novel partitivirus isolated from the phytopathogenic fungus Aplosporella javeedii - Xinru Wan; Ying Zhao; Yuanyuan Zhang; Chenxing Wei; Hongyan Du; Han Zhang; Jiahui Chen; Lijie Yang; Rui Zang; Caiyi Wen (Archives of Virology, 2021)

A novel apoptosis probe, cyclic ApoPep-1, for in vivo imaging with multimodal applications in chronic inflammatory arthritis - In-Seop So; Jin Hee Kang; Jung Wan Hong; Shijin Sung; Al Faruque Hasan; Keum Hee Sa; Seung Woo Han; In San Kim; Young Mo Kang (Apoptosis, 2021)

Contribution of root traits to variations in soil microbial biomass and community composition - Xiaohua Wan; Xinli Chen; Zhiqun Huang; Han Y. H. Chen (Plant and Soil, 2021)

Transcriptional and post-transcriptional regulation of the miR171-LaSCL6 module during somatic embryogenesis in Larix kaempferi - Qiao-Lu Zang; Yao Zhang; Su-Ying Han; Wan-Feng Li; Li-Wang Qi (Trees, 2021)
Key message Expression analysis of Larix kaempferi mature miR171s and their primary transcripts and target gene LaSCL6 during somatic embryogenesis revealed the transcriptional and post-transcriptional regulation of the miR171- LaSCL6 module. Abstract Somatic embryogenesis provides a useful experimental system for studying the regulatory mechanisms of plant development. The level and activity of microRNA171 (miR171) fluctuate during somatic embryogenesis in Larix kaempferi , but the underlying mechanisms are still unclear. Here, in L. kaempferi we identified five members of the miR171 family, which cleave LaSCL6 mRNA at different sites. In addition, we improved the method of measuring miRNA activity in a more direct way. Furthermore, we measured the expression patterns of mature miR171s and their primary transcripts during somatic embryogenesis in L. kaempferi and found that their patterns differed, indicating that the transcription of MIR171 genes and the subsequent cleavage of their intermediate products are regulated. Taken together, our findings not only offer a means to study the regulation of miRNA activity, but also provide further insight into the regulation of L . kaempferi somatic embryogenesis by miR171- LaSCL6 .

Corrigendum: Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2021)

Preparation of CuSe-PDA/g-C3N4 and its visible-light photocatalytic performance to dye degradation - Maojuan Bai; Chengcheng Xu; Xuanye Huang; Han Yin; Jun Wan (Environmental Science and Pollution Research, 2021)

Feature selection and risk prediction for patients with coronary artery disease using data mining - Nashreen Md Idris; Yin Kia Chiam; Kasturi Dewi Varathan; Wan Azman Wan Ahmad; Kok Han Chee; Yih Miin Liew (Medical & Biological Engineering & Computing, 2020)

MHC-DRB1 exon 2 polymorphism and its association with mycoplasma ovipneumonia resistance or susceptibility genotypes in sheep - Kaisheng Wang; Xianxia Liu; Qiongqiong Li; Kexing Wan; Rui Gao; Guohua Han; Chaochen Li; Mengsi Xu; Bin Jia; Xiaoyun Shen (Journal of Genetics, 2020)

Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2020)
Shark populations are constantly decreasing owing to environmental destruction and overfishing; thus, sharks are now at a risk of extinction, with 27.9% of shark species classified as endangered on the International Union for Conservation of Nature’s Red List. Sharks are apex predators and a keystone species in balancing the marine food chain; their extinction will create an imbalance of the entire marine ecosystem. Assisted reproductive technology is the last resort for protecting animals facing severe extinction. Here, as a proactive effort toward building a hormone-induced artificial insemination protocol for endangered wild sharks, we identified the possibility of germ cell maturation by administration of Ovaprim ® , a commercially produced synthetic salmon gonadotropin-releasing hormone, and calculated its optimum dosage and injection timing. The experiment was conducted on two shark species— Triakis scyllium and Triaenodon obesus . We found that intramuscular injections of 0.2 mL/kg of Ovaprim ® for male T. scyllium and T. obesus , 0.2 mL/kg + 0.5 mL/kg at a 24 h interval for female T. scyllium , and 0.2 mL/kg + 0.2 mL/kg or 0.2 mL/kg + 0.3 mL/kg at a 24 h interval for female T. obesus were optimal dose protocols. These doses effectively induced the maturation and ovulation of oocytes and the release of semen. Our results confirm that Ovaprim ® is a suitable tool for shark hormone-induced artificial insemination and indicate that this method may enable the conservation of the endangered shark species.

What factors determine the mass elevation effect of the Tibetan Plateau? - Fang Han; Li Wan; Hong-zhi Wu; Bai-ping Zhang; Lan Gao; Ge Song (Journal of Mountain Science, 2020)

Standardization of the first Korean national reference standard for snake (Gloydius brevicaudus) antivenom - Kiwon Han; Hojin Song; Chan Woong Choi; Sangmi Park; Yong Seok Kang; Kikyung Jung; Byung-Hwa Lee; Yoshimasa Takahashi; Takayuki Matsumura; Akihiko Yamamoto; Yang Jin Kim; Seung-wan Jee; et al. (Toxicological Research, 2020)

Injectable Hydrogel Containing Tauroursodeoxycholic Acid for Anti-neuroinflammatory Therapy After Spinal Cord Injury in Rats - Gong Ho Han; Seong Jun Kim; Wan-Kyu Ko; Daye Lee; Jae Seo Lee; Haram Nah; In-Bo Han; Seil Sohn (Molecular Neurobiology, 2020)

Analysis of KAP1 expression patterns and human endogenous retrovirus Env proteins in ovarian cancer - Kyung-Yoon Jeon; Eun-Ji Ko; Young Lim Oh; Hongbae Kim; Wan Kyu Eo; Ari Kim; Han Gyu Sun; Mee Sun Ock; Ki Hyung Kim; Hee-Jae Cha (Genes & Genomics, 2020)

Makran ophiolitic basalts (SE Iran) record Late Cretaceous Neotethys plume-ridge interaction - Rasoul Esmaeili; Wenjiao Xiao; Mohammad Ebrahimi; Ji’En Zhang; Zhiyong Zhang; Yasser Abd El-Rahman; Chunming Han; Bo Wan; Songjian Ao; Dongfang Song; Shirin Shahabi; Arthur Aouizerat (International Geology Review, 2020)

Evaluation and Comparison of the Toxic Effects of MgO NPs, ZnO NPs, α-Fe2O3 NPs, γ-Fe2O3 NPs, and Fe3O4 NPs on the Remediation for Cadmium-Related Effects in Wheat Seedlings - Yongchao Cheng; Yuxuan Cheng; Han Zheng; Yaxin Song; Ruizhe Li; Fengting Wan; Junli Li (Water, Air, & Soil Pollution, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Seasonal and long-term trends of sulfate, nitrate, and ammonium in PM2.5 in Beijing: implication for air pollution control - Xiaokun Han; Qingjun Guo; Yunchao Lang; Siliang Li; Ying Li; Zhaobing Guo; Jian Hu; Rongfei Wei; Liyan Tian; Yingxin Wan (Environmental Science and Pollution Research, 2020)

Low embankment dynamic response under vehicle traffic loads in arid-oasis areas - Qi Wan; Xiao-hua Yang; Pei-jie Yin; Han Bao (Journal of Mountain Science, 2020)

Association between the IL-6, IL-10, and TNFα gene polymorphisms and preterm-birth in Korean women - Seung Hun Han; Noo Ri Lee; Hyung Jun Kim; Yun Dan Kang; Jong Soo Kim; Jin Wan Park; Han Jun Jin (Genes & Genomics, 2020)

Accretionary processes and metallogenesis of the Central Asian Orogenic Belt: Advances and perspectives - Wenjiao Xiao; Dongfang Song; Brian F. Windley; Jiliang Li; Chunming Han; Bo Wan; Ji’en Zhang; Songjian Ao; Zhiyong Zhang (Science China Earth Sciences, 2020)

High prevalence and viremia of human pegivirus 2 in the HIV-infected population in Honghe Prefecture, Yunnan Province - Tianyi Li; Shixing Tang; Yingying Su; Zuoyi Bao; Xiaolin Wang; Yongjian Liu; Hanping Li; Jingwan Han; Zhichao Pei; Zhengwei Wan; Hang Fan; Yigang Tong; et al. (Archives of Virology, 2020)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Pharmacokinetic and Pharmacodynamic Modeling and Simulation Analysis of CTB-001, a Recently Developed Generic of Bivalirudin - Sungpil Han; Yo-Han Kim; Hee Youn Choi; Mi-Jo Kim; Wan Joo Kim; Hyunjung Park; Kyun-Seop Bae; Hyeong-Seok Lim (Pharmaceutical Research, 2019)

Using two contrasting methods with the same tracers to trace the main sediment source in a mountainous catchment - Han Wu; Dong-hong Xiong; Su Zhang; Yong Yuan; Wan-Xin Li; Lin Liu; Zheng-an Su; Xiao-ning Lu (Journal of Mountain Science, 2019)

A genome-wide association study of resistance to Pseudomonas plecoglossicida infection in the large yellow croaker (Larimichthys crocea) - Liang Wan; Weijia Wang; Guijia Liu; Linsong Dong; Wanbo Li; Zhaofang Han; Kun Ye; Zhiyong Wang (Aquaculture International, 2019)

A preliminary study on diet of the Yangtze finless porpoise using next‐generation sequencing techniques - Jiwei Yang; Xiaoling Wan; Xianyuan Zeng; Jinsong Zheng; Yi Han; Fei Fan; Yujiang Hao; Kexiong Wang; Zhigang Mei; Ding Wang (Marine Mammal Science, 2019)

Protein replenishment in pitcher fluids of Nepenthes × ventrata revealed by quantitative proteomics (SWATH-MS) informed by transcriptomics - Wan Nor Adibah Wan Zakaria; Wan Mohd Aizat; Hoe-Han Goh; Normah Mohd Noor (Journal of Plant Research, 2019)

Tuta absoluta continues to disperse in Asia: damage, ongoing management and future challenges - Peng Han; Yunus Bayram; Liora Shaltiel-Harpaz; Fariba Sohrabi; Anitha Saji; Uulu Tair Esenali; Anvar Jalilov; Abid Ali; Pathour R. Shashank; Khasan Ismoilov; Zhao-zhi Lu; Su Wang; et al. (Journal of Pest Science, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Geospatial relation captioning for high-spatial-resolution images by using an attention-based neural network - Jie Chen; Yarong Han; Li Wan; Xing Zhou; Min Deng (International Journal of Remote Sensing, 2019)

Integrated transcriptomic and phytochemical analyses provide insights into characteristic metabolites variation in leaves of 1-year-old grafted tea (Camellia sinensis) - Jieyun Han; Mengqian Lu; Biying Zhu; Rangjian Wang; Xiaochun Wan; Wei-Wei Deng; Zheng-Zhu Zhang (Tree Genetics & Genomes, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Chrysophanol, an anthraquinone from AST2017-01, possesses the anti-proliferative effect through increasing p53 protein levels in human mast cells - Na-Ra Han; Hee-Yun Kim; Soonsik Kang; Mi Hye Kim; Kyoung Wan Yoon; Phil-Dong Moon; Hyung-Min Kim; Hyun-Ja Jeong (Inflammation Research, 2019)

Assessment of optimal growth conditions for cultivation of the edible Caulerpa okamurae (Caulerpales, Chlorophyta) from Korea - Xu Gao; Han Gil Choi; Seo Kyoung Park; Zhong Min Sun; Ki Wan Nam (Journal of Applied Phycology, 2019)

Catalytic hydrolysis of cellulose by phosphotungstic acid–supported functionalized metal-organic frameworks with different electronegative groups - Jinye Han; Yan Wang; Jinquan Wan; Yongwen Ma (Environmental Science and Pollution Research, 2019)

Evaluating Walnut (Juglans spp.) for resistance to walnut blight and comparisons between artificial inoculation assays and field studies - Shijiao Jiang; Shan Han; Dan He; Guangli Cao; Fan Zhang; Xueqin Wan (Australasian Plant Pathology, 2019)

Application of the SeDeM Expert System in Studies for Direct Compression Suitability on Mixture of Rhodiola Extract and an Excipient - Shulin Wan; Rui Yang; Han Zhang; Xuelian Li; Mingxian Gu; Tianbing Guan; Jianbing Ren; Huimin Sun; Chuanyun Dai (AAPS PharmSciTech, 2019)

Changes of mycorrhizal fungal community occurring during the natural restoration after the chi-chi earthquake in Taiwan - Tzu-Chao Lin; Pi-Han Wang; Wan-Rou Lin (Symbiosis, 2019)

Structure and tectonic evolution of the Late Jurassic–Early Cretaceous Wandashan accretionary complex, NE China - Han Zheng; Xiaomeng Sun; Kuo Wan; Pujun Wang; Song He; Xuqing Zhang (International Geology Review, 2019)

Ursodeoxycholic Acid Inhibits Inflammatory Responses and Promotes Functional Recovery After Spinal Cord Injury in Rats - Wan-Kyu Ko; Seong Jun Kim; Min-Jae Jo; Hyemin Choi; Donghyun Lee; Il Keun Kwon; Soo-Hong Lee; In-Bo Han; Seil Sohn (Molecular Neurobiology, 2019)

A Context-Based Analgesia Model in Rats: Involvement of Prefrontal Cortex - Lingchi Xu; Yalan Wan; Longyu Ma; Jie Zheng; Bingxuan Han; Feng-Yu Liu; Ming Yi; You Wan (Neuroscience Bulletin, 2018)

LaMIR166a-mediated auxin biosynthesis and signalling affect somatic embryogenesis in Larix leptolepis - Zhe-Xin Li; Yan-Ru Fan; Shao-Fei Dang; Wan-Feng Li; Li-Wang Qi; Su-ying Han (Molecular Genetics and Genomics, 2018)

RNA-Seq-mediated transcriptomic analysis of heat stress response in a polar Chlorella sp. (Trebouxiophyceae, Chlorophyta) - Sze-Wan Poong; Kok-Keong Lee; Phaik-Eem Lim; Tun-Wen Pai; Chiew-Yen Wong; Siew-Moi Phang; Chien-Ming Chen; Cing-Han Yang; Chun-Cheng Liu (Journal of Applied Phycology, 2018)

Characterizing the Mass Elevation Effect across the Tibetan Plateau - Fang Han; Bai-ping Zhang; Fang Zhao; Li Wan; Jing Tan; Tian Liang (Journal of Mountain Science, 2018)

Nocardia seriolae infection in the cultured eel Anguilla japonica in Korea - Jin Do Kim; Nam‐Sil Lee; Jeung Wan Do; Myoung Sug Kim; Han Gill Seo; Miyoung Cho; Sung Hee Jung; Hyun‐Ja Han (Journal of Fish Diseases, 2018)
Mass mortality occurred at an Anguilla japonica eel farm equipped with a recirculating aquaculture system in Gimcheon, Korea, from late spring to early summer 2015. The cumulative 3‐month mortality was 16% (approximately 24,300–150,000 fish). The majority of affected fish displayed ulcerative lesions that progressed to petechial haemorrhages and small white granulomas in the major organs. A Gram‐positive, acid‐fast, nonmotile bacterium was isolated from internal organ lesions. Phylogenetic analysis of 16S rRNA identified the species as Nocardia seriolae and the strain was designated EM 150506. Afterwards, naïve eels were injected with 1.8 × 10 7 colony‐forming units per fish to confirm the strain's pathogenicity, which resulted in a 20% mortality rate within 4 weeks. However, surviving fish still exhibited white N. seriolae colonies in internal organs. To our knowledge, this is the first report of a N. seriolae infection in cultured eel.

Mapping Genetic Loci for Quantitative Traits of Golden Shell Color, Mineral Element Contents, and Growth-Related Traits in Pacific Oyster (Crassostrea gigas) - Junlin Song; Qi Li; Yong Yu; Sai Wan; Lichen Han; Shaojun Du (Marine Biotechnology, 2018)

Bioactive furanocoumarins from the stems and leaves of Clausena hainanensis - Yan-Lei Ma; Chao Zhang; Wan-Hui Zhao; Shi Shi; Dan-Nv He; Pan Zhang; Xiao-Hong Liu; Ting-Ting Han; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2018)

Piperlongumine Improves Lipopolysaccharide-Induced Amyloidogenesis by Suppressing NF-KappaB Pathway - Sun Mi Gu; Hee Pom Lee; Young Wan Ham; Dong Ju Son; Hoi Yeong Kim; Ki Wan Oh; Sang-Bae Han; Jaesuk Yun; Jin Tae Hong (NeuroMolecular Medicine, 2018)

Genomewide association study for economic traits in the large yellow croaker with different numbers of extreme phenotypes - Liang Wan; Linsong Dong; Shijun Xiao; Zhaofang Han; Xiaoqing Wang; Zhiyong Wang (Journal of Genetics, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Risk factors, outcomes and genotypes of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream infection: a three-year retrospective study in a large tertiary hospital in Northern China - Si-Han Zheng; Sheng-Ji Cao; Hui Xu; Dan Feng; Li-Ping Wan; Guang-Jie Wang; Xiao-Guang Xiao (Infectious Diseases, 2018)

Novel TBX22 mutations in Chinese nonsyndromic cleft lip/palate families - Jiewen Dai; Chen Xu; Guomin Wang; Yun Liang; Teng Wan; Yong Zhang; Xiaofeng Xu; Lebin Yu; Zonggang Che; Qiqing Han; Dandan Wu; Yusheng Yang (Journal of Genetics, 2018)

Uncovering tea-specific secondary metabolism using transcriptomic and metabolomic analyses in grafts of Camellia sinensis and C. oleifera - Wei-Wei Deng; Jieyun Han; Yanbing Fan; Yuling Tai; Biying Zhu; Mengqian Lu; Rangjian Wang; Xiaochun Wan; Zheng-Zhu Zhang (Tree Genetics & Genomes, 2018)

PKM2 knockdown influences SREBP activation and lipid synthesis in bovine mammary-gland epithelial MAC-T cells - Bing-Qian Su; Ying-Qian Han; Shuang-Shuang Fan; Sheng-Li Ming; Bo Wan; Wei-Fei Lu; Bei-Bei Chu; Guo-Yu Yang; Jiang Wang (Biotechnology Letters, 2018)

Transcriptome sequencing of an Antarctic microalga, Chlorella sp. (Trebouxiophyceae, Chlorophyta) subjected to short-term ultraviolet radiation stress - Sze-Wan Poong; Phaik-Eem Lim; Siew-Moi Phang; Chiew-Yen Wong; Tun-Wen Pai; Chien-Ming Chen; Cing-Han Yang; Chun-Cheng Liu (Journal of Applied Phycology, 2018)

Growth, reproduction and recruitment of Silvetia siliquosa (Fucales, Phaeophyceae) transplants using polyethylene rope and natural rock methods - Xu Gao; Han Gil Choi; Seo Kyoung Park; Jung Rok Lee; Jeong Ha Kim; Zi-Min Hu; Ki Wan Nam (Algae, 2017)

(E)-2-Methoxy-4-(3-(4-methoxyphenyl) prop-1-en-1-yl) Phenol Ameliorates LPS-Mediated Memory Impairment by Inhibition of STAT3 Pathway - Ji Yeon Choi; Chul Ju Hwang; Do Yeon Lee; Sun Mi Gu; Hee Pom Lee; Dong Young Choi; Ki Wan Oh; Sang-Bae Han; Jin Tae Hong (NeuroMolecular Medicine, 2017)

Activation of Alpha-7 Nicotinic Acetylcholine Receptor Reduces Brain Edema in Mice with Ischemic Stroke and Bone Fracture - Dingquan Zou; Man Luo; Zhenying Han; Lei Zhan; Wan Zhu; Shuai Kang; Chen Bao; Zhao Li; Jeffrey Nelson; Rui Zhang; Hua Su (Molecular Neurobiology, 2017)

MIR166a Affects the Germination of Somatic Embryos in Larixleptolepis by Modulating IAA Biosynthesis and Signaling Genes - Zhe-Xin Li; Li-Feng Zhang; Wan-Feng Li; Li-Wang Qi; Su-Ying Han (Journal of Plant Growth Regulation, 2017)

Wart-like spot formation on the fronds of Chondrus ocellatus (Gigartinales) by a brown alga, Mikrosyphar zosterae (Ectocarpales) in Korea - Cyr Abel Maranguy Ogandaga; Yeon Ju Na; Sang-Rae Lee; Young Sik Kim; Han Gil Choi; Ki Wan Nam (Journal of Applied Phycology, 2017)

Di-2-pyridylketone 4,4-dimethyl-3-thiosemicarbazone (Dp44mT), an anticancer agent, exerts an anti-inflammatory effect in activated human mast cells - Sun-Young Nam; Na-Ra Han; Kyoung Wan Yoon; Hyung-Min Kim; Hyun-Ja Jeong (Inflammation Research, 2017)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

Sequential combination of docetaxel with a SHP-1 agonist enhanced suppression of p-STAT3 signaling and apoptosis in triple negative breast cancer cells - Chun-Yu Liu; Kuen-Feng Chen; Tzu-I Chao; Pei-Yi Chu; Chun-Teng Huang; Tzu-Ting Huang; Hsiu-Ping Yang; Wan-Lun Wang; Chia-Han Lee; Ka-Yi Lau; Wen-Chun Tsai; Jung-Chen Su; et al. (Journal of Molecular Medicine, 2017)

Anatomy of composition and nature of plate convergence: Insights for alternative thoughts for terminal India-Eurasia collision - WenJiao Xiao; SongJian Ao; Lei Yang; ChunMing Han; Bo Wan; Ji’En Zhang; ZhiYong Zhang; Rui Li; ZhenYu Chen; ShuaiHua Song (Science China Earth Sciences, 2017)

Experimentally increased water and nitrogen affect root production and vertical allocation of an old-field grassland - Zhuwen Xu; Haiyan Ren; Mai-He Li; Ivano Brunner; Jinfei Yin; Heyong Liu; Deliang Kong; Xiao-Tao Lü; Tao Sun; Jiangping Cai; Ruzhen Wang; Yongyong Zhang; et al. (Plant and Soil, 2017)

Transcriptome analysis provides insights into wood formation during larch tree aging - Wan-Feng Li; Wen-Hua Yang; Shou-Gong Zhang; Su-Ying Han; Li-Wang Qi (Tree Genetics & Genomes, 2017)

The role of surface functionalization on the pulmonary inflammogenicity and translocation into mediastinal lymph nodes of graphene nanoplatelets in rats - Jong Kwon Lee; A Young Jeong; Jiyeong Bae; Ji Hyun Seok; Jun-Young Yang; Hang Sik Roh; Jiyoung Jeong; Youngju Han; Jayoung Jeong; Wan-Seob Cho (Archives of Toxicology, 2017)

Streptomyces luozhongensis sp. nov., a novel actinomycete with antifungal activity and antibacterial activity - Renwen Zhang; Xiaoxue Han; Zhanfeng Xia; Xiaoxia Luo; Chuanxing Wan; Lili Zhang (Antonie van Leeuwenhoek, 2017)

Geochemistry of fine-grained clastic rocks in the Mesoproterozoic Kawabulake Group: implications for provenance and the tectonic model of the Eastern Tianshan, Xinjiang, NW China - Deng-Feng Li; Hua-Yong Chen; Li Zhang; Philip Fralick; Pete Hollings; Mei Mi; Wan-Jian Lu; Jin-Sheng Han; Cheng-Ming Wang; Jing Fang (International Journal of Earth Sciences, 2017)

Growth responses of Chondrus ocellatus Holmes (Gigartinales, Rhodophyta) to two endophytes, Mikrosyphar zosterae Kuckuck (Ectocarpales, Ochrophyta) and Ulvella ramosa (N. L. Gardner) R. Nielsen (Ulvales, Chlorophyta) in culture - Cyr Abel Maranguy Ogandaga; Han Gil Choi; Jang Kyun Kim; Ki Wan Nam (Algae, 2016)

Development of serological procedures for sensitive, rapid detection of Cucumber mosaic virus in Lilium - Han Sol Kim; Dong Wan Kim; Yong-Tae Jung (Horticulture, Environment, and Biotechnology, 2016)

Identification of odor volatile compounds and deodorization of Paphia undulata enzymatic hydrolysate - Deke Chen; Xin Chen; Hua Chen; Bingna Cai; Peng Wan; Xiaolian Zhu; Han Sun; Huili Sun; Jianyu Pan (Journal of Ocean University of China, 2016)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Persistent infiltration and pro-inflammatory differentiation of monocytes cause unresolved inflammation in brain arteriovenous malformation - Rui Zhang; Zhenying Han; Vincent Degos; Fanxia Shen; Eun-Jung Choi; Zhengda Sun; Shuai Kang; Michael Wong; Wan Zhu; Lei Zhan; Helen M. Arthur; S. Paul Oh; et al. (Angiogenesis, 2016)

Depot-specific effects of treadmill running and rutin on white adipose tissue function in diet-induced obese mice - Neng Chen; Ting Lei; Lili Xin; Lingmei Zhou; Jinbo Cheng; Liqiang Qin; Shufen Han; Zhongxiao Wan (Journal of Physiology and Biochemistry, 2016)

Descending thin limb of the intermediate loop expresses both aquaporin 1 and urea transporter A2 in the mouse kidney - Wan-Young Kim; Hyun-Wook Lee; Ki-Hwan Han; Sun-Ah Nam; Arum Choi; Yong-Kyun Kim; Jin Kim (Histochemistry and Cell Biology, 2016)

Thiacremonone Potentiates Anti-Oxidant Effects to Improve Memory Dysfunction in an APP/PS1 Transgenic Mice Model - Hyung-Mun Yun; Peng Jin; Kyung-Ran Park; JaeRyun Hwang; Heon-Sang Jeong; Eun-Cheol Kim; Jea-Kyung Jung; Ki-Wan Oh; Bang Yeon Hwang; Sang Bae Han; Jin Tae Hong (Molecular Neurobiology, 2016)

Reproductive responses of male Brandt’s voles (Lasiopodomys brandtii) to 6-methoxybenzoxazolinone (6-MBOA) under short photoperiod - Xin Dai; Lian Yu Jiang; Mei Han; Man Hong Ye; Ai Qin Wang; Wan Hong Wei; Sheng Mei Yang (The Science of Nature, 2016)

The application study on the multi-scales integrated prediction method to fractured reservoir description - Shuang-Quan Chen; Lian-Bo Zeng; Ping Huang; Shao-Han Sun; Wan-Lu Zhang; Xiang-Yang Li (Applied Geophysics, 2016)

Effect of mevalonic acid on cholesterol synthesis in bovine intramuscular and subcutaneous adipocytes - Xiaomu Liu; Wei You; Haijian Cheng; Qingfeng Zhang; Enliang Song; Fachun Wan; Hong Han; Guifen Liu (Journal of Applied Genetics, 2016)

Klf10 regulates odontoblast differentiation and mineralization via promoting expression of dentin matrix protein 1 and dentin sialophosphoprotein genes - Zhuo Chen; Wentong Li; Han Wang; Chunyan Wan; Daoshu Luo; Shuli Deng; Hui Chen; Shuo Chen (Cell and Tissue Research, 2016)

Changes in digestive enzyme activities during larval development of Chinese loach Paramisgurnus dabryanus (Dabry de Thiersant, 1872) - Yun-Long Zhang; Qiao-Wan Wu; Wei-Hua Hu; Fan Wang; Zhong-Bo Zhao; Hui He; Wei-Han Shao; Qi-Xue Fan (Fish Physiology and Biochemistry, 2015)

Complete genome sequence and comparative genome analysis of Streptococcus parauberis KCTC11980 - Jung Soo Seo; Mun Gyeong Kwon; Jee Youn Hwang; Sung Hee Jung; Hyun Ja Han; Myoung Sug Kim; Jeong-Wan Do; Myoung Ae Park; Dong-Wook Kim; Wang Sik Cho; Kyungho Lee (Genes & Genomics, 2015)

Toxic response of graphene nanoplatelets in vivo and in vitro - Eun-Jung Park; Gwang-Hee Lee; Beom Seok Han; Byoung-Seok Lee; Somin Lee; Myung-Haing Cho; Jae-Ho Kim; Dong-Wan Kim (Archives of Toxicology, 2015)

Neuroinflammatory and Amyloidogenic Activities of IL-32β in Alzheimer’s Disease - Hyung-Mun Yun; Jin A. Kim; Chul Ju Hwang; Peng Jin; Myung Ki Baek; Jin Moo Lee; Ji Eun Hong; Sang Min Lee; Sang Bae Han; Ki Wan Oh; Dong Young Choi; Do Young Yoon; et al. (Molecular Neurobiology, 2015)

Memory Impairment in Estrogen Receptor α Knockout Mice Through Accumulation of Amyloid-β Peptides - Chul Ju Hwang; Hyung-Mun Yun; Kyung-Ran Park; Ju Kyung Song; Hyun Ok Seo; Byung Kook Hyun; Dong Young Choi; Hwan-Soo Yoo; Ki-Wan Oh; Dae Yeun Hwang; Sang-Bae Han; Jin Tae Hong (Molecular Neurobiology, 2015)

Size-dependent clearance of gold nanoparticles from lungs of Sprague–Dawley rats after short-term inhalation exposure - Sung Gu Han; Jong Seong Lee; Kangho Ahn; Yong Soon Kim; Jin Kwon Kim; Ji Huyn Lee; Jae Hoon Shin; Ki Soo Jeon; Wan Seob Cho; Nam Woong Song; Mary Gulumian; Beom Soo Shin; et al. (Archives of Toxicology, 2015)

CARD9 Deficiencies Linked to Impaired Neutrophil Functions Against Phialophora verrucosa - Pin Liang; Xiaowen Wang; Runchao Wang; Zhe Wan; Wenling Han; Ruoyu Li (Mycopathologia, 2015)

Reducing Effect of IL-32α in the Development of Stroke Through Blocking of NF-κB, but Enhancement of STAT3 Pathways - Chul Ju Hwang; Hyung-Mun Yun; Yu Yeon Jung; Dong Hun Lee; Na Young Yoon; Hyun Ok Seo; Jin-Yi Han; Ki-Wan Oh; Dong Young Choi; Sang-Bae Han; Do Young Yoon; Jin Tae Hong (Molecular Neurobiology, 2015)

Effects of wave action and grazers on frond perforation of the green alga, Ulva australis - Han Gil Choi; Bo Yeon Kim; Seo Kyoung Park; Jin Suk Heo; Changsong Kim; Young Sik Kim; Ki Wan Nam (Algae, 2015)

Danggui Sini Decoction Ameliorates Myelosuppression in Animal Model by Upregulating Thrombopoietin Expression - Qing-quan Chen; Xuesong Han; Wan-ming Wang; Liangyu Zhao; Aimin Chen (Cell Biochemistry and Biophysics, 2015)

Desertification assessments in the Hexi corridor of northern China’s Gansu Province by remote sensing - Lanying Han; Zhengcai Zhang; Qiang Zhang; Xin Wan (Natural Hazards, 2015)

KHSRP Participates in Manganese-Induced Neurotoxicity in Rat Striatum and PC12 Cells - Shangshi Shi; Jianya Zhao; Lingling Yang; Xiaoke Nie; Jingling Han; Xia Ma; Chunhua Wan; Junkang Jiang (Journal of Molecular Neuroscience, 2015)

Effects of experimentally-enhanced precipitation and nitrogen on resistance, recovery and resilience of a semi-arid grassland after drought - Zhuwen Xu; Haiyan Ren; Jiangping Cai; Ruzhen Wang; Mai-He Li; Shiqiang Wan; Xingguo Han; Bernard J. Lewis; Yong Jiang (Oecologia, 2014)

Soil Characteristics in Relation to Vegetation Communities in the Wetlands of Poyang Lake, China - Wang Xiaolong; Han Jingyi; Xu Ligang; Wan Rongrong; Chen Yuwei (Wetlands, 2014)

New records of three endophytic green algae from Grateloupia spp. (Rhodophyta) in Korea - Chansong Kim; Young Sik Kim; Han Gil Choi; Ki Wan Nam (Algae, 2014)

Tectonic implications of Re-Os dating of molybdenum deposits in the Tianshan–Xingmeng Orogenic Belt, Central Asia - Chunming Han; Wenjiao Xiao; Guochun Zhao; Benxun Su; Songjian Ao; Jien Zhang; Zhiyong Zhang; Bo Wan; Zhongmei wang (International Geology Review, 2014)

Planning the priority protected areas of endangered orchid species in northeastern China - Jizhong Wan; Chunjing Wang; Shijie Han; Jinghua Yu (Biodiversity and Conservation, 2014)

Cloning and characterization of four differentially expressed cDNAs encoding NFYA homologs involved in responses to ABA during somatic embryogenesis in Japanese larch (Larix leptolepis) - Li-feng Zhang; Wan-feng Li; Hai-yan Xu; Li-wang Qi; Su-ying Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Regulation of synchronism by abscisic-acid-responsive small noncoding RNAs during somatic embryogenesis in larch (Larix leptolepis) - Jun-Hong Zhang; Shou-Gong Zhang; Shui-Gen Li; Su-Ying Han; Wan-Feng Li; Xin-Min Li; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

The post-transcriptional regulation of LaSCL6 by miR171 during maintenance of embryogenic potential in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Tree Genetics & Genomes, 2014)

Salinity changes in the anadromous river pufferfish, Takifugu obscurus, mediate gene regulation - Su-Young Jeong; Jin-Hyoung Kim; Wan-Ok Lee; Hans-Uwe Dahms; Kyung-Nam Han (Fish Physiology and Biochemistry, 2014)

(E)-2,4-Bis(p-hydroxyphenyl)-2-butenal inhibits tumor growth via suppression of NF-κB and induction of death receptor 6 - Jung Ok Ban; Young-Suk Jung; Dae Hwan Kim; Kyung-Ran Park; Hyung-Mun Yun; Nam Jin Lee; Hee Pom Lee; Jeong-Hyun Shim; Heon-Sang Jeong; Yun-Hee Lee; Young Wan Ham; Sang-Bae Han; et al. (Apoptosis, 2014)

High dose of extracellular ATP switched autophagy to apoptosis in anchorage-dependent and anchorage-independent hepatoma cells - Qing Wei; Ying Zhang; Lei Sun; Xiaoqing Jia; Wanwan Huai; Chengcheng Yu; Zhengkun Wan; Lihui Han (Purinergic Signalling, 2013)

Acceleration of the Development of Alzheimer’s Disease in Amyloid Beta-Infused Peroxiredoxin 6 Overexpression Transgenic Mice - Hyung-Mun Yun; Peng Jin; Jin-Yi Han; Moon-Soon Lee; Sang-Bae Han; Ki-Wan Oh; Sung-Han Hong; Eun-Yong Jung; Jin Tae Hong (Molecular Neurobiology, 2013)

Molecular and immunohistochemical characterization of the chitinase gene from Pieris rapae granulovirus - Seunghan Oh; Dong Hyun Kim; Bharat Bhusan Patnaik; Yong Hun Jo; Mi Young Noh; Hyo Jeong Lee; Kwang Ho Lee; Kwang Ho Yoon; Wan-Jong Kim; Ju Young Noh; Heon Cheon Jeong; Yong Seok Lee; et al. (Archives of Virology, 2013)

Palaeozoic porphyry Cu–Au and ultramafic Cu–Ni deposits in the eastern Tianshan orogenic belt: temporal constraints from U–Pb geochronology - Zhongkun Han; Chunming Han; Wenjiao Xiao; Guochun Zhao; Zhongmei Wang; Songjian Ao; Jien Zhang; Bo Wan (International Geology Review, 2013)

Regulation of LaMYB33 by miR159 during maintenance of embryogenic potential and somatic embryo maturation in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Prediction of the tacrolimus population pharmacokinetic parameters according to CYP3A5 genotype and clinical factors using NONMEM in adult kidney transplant recipients - Nayoung Han; Hwi-yeol Yun; Jin-yi Hong; In-Wha Kim; Eunhee Ji; Su Hyun Hong; Yon Su Kim; Jongwon Ha; Wan Gyoon Shin; Jung Mi Oh (European Journal of Clinical Pharmacology, 2013)

AMPK activation reduces vascular permeability and airway inflammation by regulating HIF/VEGFA pathway in a murine model of toluene diisocyanate-induced asthma - Seoung Ju Park; Kyung Sun Lee; So Ri Kim; Han Jung Chae; Wan Hee Yoo; Dong Im Kim; Myoung Shin Jeon; Yong Chul Lee (Inflammation Research, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Morphological and biochemical differences in three Undaria pinnatifida populations in Korea - Kwang-Jae Park; Bo-Yeon Kim; Seo-Kyoung Park; Jong-Hwa Lee; Young-Sik Kim; Han-Gil Choi; Ki-Wan Nam (Algae, 2012)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

Description of Fimbriimonas ginsengisoli gen. nov., sp. nov. within the Fimbriimonadia class nov., of the phylum Armatimonadetes - Wan-Taek Im; Zi-Ye Hu; Kyoung-Ho Kim; Sung-Keun Rhee; Han Meng; Sung-Taik Lee; Zhe-Xue Quan (Antonie van Leeuwenhoek, 2012)

N-Nitrosodimethylamine induced lung fibroblast cell death is associated with JNK activation - Bo Li; Do-Sung Kim; Hyo-Won Oh; Hyun-Dae Lim; Wan Lee; Ki Yon Rhew; Hyung-Ryong Kim; Han-Jung Chae (Molecular & Cellular Toxicology, 2012)

Elevated skin autofluorescence is strongly associated with foot ulcers in patients with diabetes: a cross-sectional, observational study of Chinese subjects - Hang Hu; Chun-mao Han; Xin-lei Hu; Wan-lan Ye; Wen-juan Huang; Andries J. Smit (Journal of Zhejiang University-SCIENCE B, 2012)

Clinical and genetic factors affecting tacrolimus trough levels and drug-related outcomes in Korean kidney transplant recipients - In-Wha Kim; Yoo Jin Moon; Eunhee Ji; Kyung Im Kim; Nayoung Han; Sung Ju Kim; Wan Gyoon Shin; Jongwon Ha; Jeong-Hyun Yoon; Hye Suk Lee; Jung Mi Oh (European Journal of Clinical Pharmacology, 2012)

Formaldehyde up-regulates TRPV1 through MAPK and PI3K signaling pathways in a rat model of bone cancer pain - Ying Han; Yan Li; Xing Xiao; Jia Liu; Xiang-Ling Meng; Feng-Yu Liu; Guo-Gang Xing; You Wan (Neuroscience Bulletin, 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

Co-delivery of Adenovirus and Carmustine by Anionic Liposomes with Synergistic Anti-tumor Effects - Zhirong Zhong; Yu Wan; Sanjun Shi; Jianfeng Han; Zhirong Zhang; Xun Sun (Pharmaceutical Research, 2012)

Comparison of Bacterial and Fungal Communities Between Natural and Planted Pine Forests in Subtropical China - Ming Nie; Han Meng; Ke Li; Jia-Rong Wan; Zhe-Xue Quan; Chang-Ming Fang; Jia-Kuan Chen; Bo Li (Current Microbiology, 2012)

A novel role of andrographolide, an NF-kappa B inhibitor, on inhibition of platelet activation: the pivotal mechanisms of endothelial nitric oxide synthase/cyclic GMP - Wan-Jung Lu; Jie-Jen Lee; Duen-Suey Chou; Thanasekaran Jayakumar; Tsorng-Han Fong; George Hsiao; Joen-Rong Sheu (Journal of Molecular Medicine, 2011)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Expression of a novel gene FAM43B repressing cell proliferation is regulated by DNA methylation in hepatocellular carcinoma cell lines - Xiao Xu; Rui-Fang Liu; Bing-Bing Wan; Wen-Ming Xing; Jian Huang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2011)

Effect of fiducial marker defects on stereotactic target localization in the Leksell stereotactic system - Jeong-Hoon Park; Jung Ho Han; Chae-Yong Kim; Chang Wan Oh; Dong Gyu Kim; Tae-Suk Suh; Hyun-Tai Chung (Medical & Biological Engineering & Computing, 2011)

Isolation and expression analysis of LEA genes in peanut (Arachis hypogaea L.) - Lei Su; Chuan-Zhi Zhao; Yu-Ping Bi; Shu-Bo Wan; Han Xia; Xing-Jun Wang (Journal of Biosciences, 2011)

Molecular cloning and characterization of Izumo1 gene from sheep and cashmere goat reveal alternative splicing - Wan-Jin Xing; Bao-Da Han; Qi Wu; Li Zhao; Xiao-Hong Bao; Shorgan Bou (Molecular Biology Reports, 2011)

26-Week carcinogenicity study of di-isodecyl phthalate by dietary administration to CB6F1-rasH2 transgenic mice - Wan-Seob Cho; Jayoung Jeong; Mina Choi; Sue Nie Park; Beom Seok Han; Woo-Chan Son (Archives of Toxicology, 2011)

Carcinogenicity study of 3-monochloropropane-1, 2-diol (3-MCPD) administered by drinking water to B6C3F1 mice showed no carcinogenic potential - Jayoung Jeong; Beom Seok Han; Wan-Seob Cho; Mina Choi; Chang-Su Ha; Byoung-Seok Lee; Yong-Bum Kim; Woo-Chan Son; Choong-Yong Kim (Archives of Toxicology, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Increased temperature and precipitation interact to affect root production, mortality, and turnover in a temperate steppe: implications for ecosystem C cycling - WENMING BAI; SHIQIANG WAN; SHULI NIU; WEIXING LIU; QUANSHENG CHEN; QIBING WANG; WENHAO ZHANG; XINGGUO HAN; LINGHAO LI (Global Change Biology, 2010)
Fine root production and turnover play important roles in regulating carbon (C) cycling in terrestrial ecosystems. In order to examine effects of climate change on root production and turnover, a field experiment with increased temperature and precipitation had been conducted in a semiarid temperate steppe in northern China since April 2005. Experimental warming decreased annual root production, mortality, and mean standing crop by 10.3%, 12.1%, 7.0%, respectively, while root turnover was not affected in 2006 and 2007 by the warming. Annual root production and turnover was 5.9% and 10.3% greater in the elevated than ambient precipitation plots. Changes in root production and mortality in response to increased temperature and precipitation could be largely attributed to the changes in gross ecosystem productivity (GEP) and belowground/aboveground C allocation. There were significant interactive effects of warming and increased precipitation on root productivity, mortality, and standing crop. Experimental warming had positive and negative effects on the three root variables (root production, mortality, standing crop) under ambient and increased precipitation, respectively. Increased precipitation stimulated and suppressed the three root variables in the unwarmed and warmed subplots, respectively. The positive dependence of soil respiration and ecosystem respiration upon root productivity and mortality highlights the important role of root dynamics in ecosystem C cycling. The nonadditive effects of increased temperature and precipitation on root productivity, mortality, and standing crop observed in this study are critical for model projections of climate–ecosystem feedbacks. These findings indicate that carbon allocation is a focal point for future research and that results from single factor experiments should be treated with caution because of factor interactions.

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Nitrogen effects on net ecosystem carbon exchange in a temperate steppe - SHULI NIU; MINGYU WU; YI HAN; JIANGYANG XIA; ZHE ZHANG; HAIJUN YANG; SHIQIANG WAN (Global Change Biology, 2010)
It has widely been documented that nitrogen (N) enrichment stimulates plant growth and net primary production. However, there is still dispute on how N addition affects net ecosystem CO 2 exchange (NEE), which represents the balance between ecosystem carbon (C) uptake and release. We conducted an experimental study to examine effects of N addition on NEE in a temperate steppe in northern China from 2005 to 2008. N was added at a rate of 10 g N m −2 yr −1 with NH 4 NO 3 alone or in combination with phosphorous (P, 5 g P 2 O 5 m −2 yr −1 ) in both clipped and unclipped plots. Over the 4 years, N addition significantly stimulated growing‐season NEE, on average, by 27%. Neither the main effects of P addition or clipping nor their interactions with N addition were statistically significant on NEE in any of the 4 years. However, the magnitude of N stimulation on NEE declined over time. N addition significantly increased NEE by 60% in 2005 and 21% in 2006, but its effect was not significant in 2007 and 2008. N‐induced shift in species composition was primarily responsible for the declined N stimulation over time. The gradually increasing coverage of the upper canopy species ( Stipa krylovii ) and standing litter accumulation induced light limitation on the lower canopy species ( Artemisia frigida ). Thus, N‐induced shifts in plant species composition strongly regulated the direct effects of N addition on C sequestration in the temperate steppe.

Non-Additive Effects of Water and Nitrogen Addition on Ecosystem Carbon Exchange in a Temperate Steppe - Shuli Niu; Haijun Yang; Zhe Zhang; Mingyu Wu; Qi Lu; Linghao Li; Xingguo Han; Shiqiang Wan (Ecosystems, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

Temporal Variations in Seaweed Biomass in Korean Coasts: Woejodo and Jusamdo, Jeonbuk - Han-Gil Choi; Ki-Hun Lee; Xiao Qin Wan; Hyun-Il Yoo; Hyang-Ha Park; Jeong-Ha Kim; Ik-Kyo Chung (Algae, 2008)

Molecular cloning, tissue distribution and bioinformatics analyses of the rabbit BK channel β1 subunit gene - Xiao-Yong Zhang; Sha Wang; Zhen Yan; Yi Wan; Wei Wang; Guang-Bin Cui; Pang Du; Ke-Jun Ma; Wei Han; Ying-Qi Zhang; Jing-Guo Wei (Molecular Biology Reports, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Physiological differences in the growth of Sargassum horneri between the germling and adult stages - Han Gil Choi; Ki Hoon Lee; Hyun Il Yoo; Pil Jun Kang; Young Sik Kim; Ki Wan Nam (Journal of Applied Phycology, 2008)

Mesozoic paleogeography and tectonic evolution of South China Sea and adjacent areas in the context of Tethyan and Paleo‐Pacific interconnections - Di Zhou; Zhen Sun; Han‐zong Chen; He‐hua Xu; Wan‐yin Wang; Xiong Pang; Dong‐sheng Cai; Deng‐ke Hu (Island Arc, 2008)
During the Mesozoic era, the South China Sea and its environs were located at the south‐eastern margin of the Eurasian continent. There has been hot debate on the influences of Tethyan and Paleo‐Pacific tectonics to the Mesozoic evolution of the area. This paper compiles lithofacies maps of six time slices and discusses the paleogeographic and tectonic evolution of the area based on this compilation and other data on structural deformation and magmatism. In the Early Triassic, the Paleotethys Ocean extended eastward to the study area through the Song Da passage. Then a significant east–west differential evolution began. In the Late Triassic, the western area uplifted as a result of the collision between the Indosinian and South China blocks during the Indosinian orogeny, and the Song Da passage has closed since then. Meanwhile, a transgression of Paleo‐Pacific waters occurred in the eastern and south‐eastern portions of the area, forming the ‘East Guangdong–North‐west Borneo Sea’. In the Early Jurassic, seawater transgression was even more pronounced, resulting into the connection of this sea with the Mesotethys Ocean to the west. Large quantities of Tethyan water carrying Tethyan organisms entered the area. In the Middle Jurassic, a short‐lived transgression occurred in the eastern Mesotethys and resulted in the formation of the ‘Yunnan–Burma Sea’. The Late Jurassic to Early Cretaceous was the climax of the subduction of both the Mesotethys and Paleo‐Pacific towards the Eurasian continent. This led to the formation of the great ‘Circum South‐east Asia Subduction–Accretion Zone’ in the Middle or Late Cretaceous. This paper also presents various lines of evidence for a newly recognized segment of this Mesozoic subduction–accretion zone buried under Cenozoic sediments in the north‐eastern South China Sea.

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Responses of microbial biomass and respiration of soil to topography, burning, and nitrogen fertilization in a temperate steppe - Weixing Liu; Wenhua Xu; Yi Han; Changhui Wang; Shiqiang Wan (Biology and Fertility of Soils, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Physiological and chemical characteristics of field-and mountain-cultivated ginseng roots - Yong Eui Choi; Yong Suk Kim; Myong Jong Yi; Wan Geun Park; Jae Seon Yi; Seong Ryeol Chun; Sang Sup Han; Sung Jae Lee (Journal of Plant Biology, 2007)

Growth and reproductive patterns of Undaria pinnatifida sporophytes in a cultivation farm in Busan, Korea - Han Gil Choi; Young Sik Kim; Soon Jeong Lee; Ki Wan Nam (Journal of Applied Phycology, 2007)

Geochemical characterization of the organic matter, pore water constituents and shallow methane gas in the eastern part of the Ulleung Basin, East Sea (Japan Sea) - Ji‐Hoon Kim; Myong‐Ho Park; Urumu Tsunogai; Tae‐Jin Cheong; Byong‐Jae Ryu; Young‐Joo Lee; Hyun‐Chul Han; Jae‐Ho Oh; Ho‐Wan Chang (Island Arc, 2007)
Geochemical analyses of sediments, pore water and headspace gas of the piston cores taken from the eastern part of Ulleung Basin of the East Sea (Japan Sea) were carried out to assess the origin of the sedimentary organic matter and interstitial fluid. Several tephra layers within the core are identified as the Ulleung‐Oki (10.1 ka), the Aira‐Tanzawa (23 ka) and the Ulleung‐Yamato (30.9 ka) tephras. With the exception of these volcanic layers, the cores consist predominantly of muddy sediments that contain >0.5% total organic carbon. Atomic C/N ratios and δ 13 C org values suggest that the organic matter originated from marine algae rather than from land vascular plants, whereas Rock‐Eval pyrolysis suggests that the organic matter is thermally immature and comes from a land vascular plant (Type III). These conflicting results seem to be caused by the heavy oxidization of the marine organic matter. Sulphate concentration profiles of pore waters show strongly linear depletion ( r 2 > 0.97) with sediment depth. The estimated sulphate–methane interface (SMI) depth using the sulphate concentration gradient was nearly 3.5 m below seafloor (mbsf) in the southern part of the study area, and deeper than 6 mbsf in the northern part of the area. The difference in SMI depths is likely associated with the amount of the methane flux. The methane concentration below the SMI in the two southern cores increases rapidly, implying the occurrence of methanogenesis and anaerobic methane oxidation (AMO). In contrast, the two northern cores have a low methane concentration below the SMI. values measured from all cores were in the range of −83.5 to −69.5‰, which suggests that the methane derives from a methanogenic microbe. values become decreased toward SMI, but increased below SMI; therefore, has eventually the minimum value near the SMI. The values are also decreased when the methane concentration is increased. These phenomena support the typical occurrence of AMO in the study area.

Efficient transient expression and transformation of PEG-mediated gene uptake into mesophyll protoplasts of pepper (Capsicum annuum L.) - Joo Mi Jeon; Nam Young Ahn; Bo Hwa Son; Cha Young Kim; Chang-deok Han; Gun-Do Kim; Sang Wan Gal; Sung-Ho Lee (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

The distribution and economic losses of alien species invasion to China - Haigen Xu; Hui Ding; Mingyan Li; Sheng Qiang; Jianying Guo; Zhengmin Han; Zongguo Huang; Hongying Sun; Shunping He; Hairong Wu; Fanghao Wan (Biological Invasions, 2006)

Cloning of a novel human NHEDC1 (Na+/H+ exchanger like domain containing 1) gene expressed specifically in testis - Guangming Ye; Cong Chen; Dingding Han; Xiabin Xiong; Yahui Kong; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Antitumor activities of D-glucosamine and its derivatives - Li Zhang; Wan-shun Liu; Bao-qin Han; Yan-fei Peng; Dong-feng Wang (Journal of Zhejiang University-SCIENCE B, 2006)

Sensitivity enhancement of spectral surface plasmon resonance biosensors for the analysis of protein arrays - Jong Seol Yuk; Duk-Geun Hong; Jae-Wan Jung; Se-Hui Jung; Hyun-Soo Kim; Jeong-A Han; Young-Myeong Kim; Kwon-Soo Ha (European Biophysics Journal, 2006)

The status and causes of alien species invasion in China - Haigen Xu; Sheng Qiang; Zhengmin Han; Jianying Guo; Zongguo Huang; Hongying Sun; Shunping He; Hui Ding; Hairong Wu; Fanghao Wan (Biodiversity and Conservation, 2006)

Utilization of homoserine lactone as a sole source of carbon and energy by soil Arthrobacter and Burkholderia species - Wan-Wan Yang; Jong-In Han; Jared Renton Leadbetter (Archives of Microbiology, 2006)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.

Foliar Nitrogen Dynamics and Nitrogen Resorption of a Sandy Shrub Salix gordejevii in Northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Jian-Hui Huang; Shi-Qiang Wan (Plant and Soil, 2005)

Effects of daylength, irradiance and settlement density on the growth and reproduction of Undaria pinnatifida gametophytes - Han Gil Choi; Young Sik Kim; Soon Jeong Lee; Eun Jeong Park; Ki Wan Nam (Journal of Applied Phycology, 2005)

Soil characteristics and nitrogen resorption in Stipa krylovii native to northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Jian-Hui Huang; Gao-Ming Jiang; Shi-Qiang Wan (Plant and Soil, 2005)

An interspecific somatic hybrid between Actinidia chinensis and Actinidia kolomikta and its chilling tolerance - Zun-an Xiao; Lin-chen Wan; Bi-wen Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Acetylcholine induces Ca 2+ oscillations via m3/m4 muscarinic receptors in the mouse oocyte - Dawon Kang; Jae-Yong Park; Jaehee Han; In-Ha Bae; Sook-Young Yoon; Sang Soo Kang; Wan Sung Choi; Seong-Geun Hong (Pflügers Archiv - European Journal of Physiology, 2003)

Prevention of Autoimmune Insulitis by Delivery of Interleukin-4 Plasmid Using a Soluble and Biodegradable Polymeric Carrier - Minhyung Lee; Jae Joon Koh; Sang-oh Han; Kyung Soo Ko; Sung Wan Kim (Pharmaceutical Research, 2002)

Nutrient Losses from a Paddy Field Plot in Central Korea - Jae-Young Cho; Kwang-Wan Han (Water, Air, & Soil Pollution, 2002)

Effect of four chlorophytes on larval survival, development and adult body size of the mosquito Aedes aegypti - Rohani Ahmad; Wan-Loy Chu; Han-Lim Lee; Siew-Moi Phang (Journal of Applied Phycology, 2001)

Expression of Bacillus macerans cyclodextrin glucanotransferase gene in Saccharomyces cerevisiae - Soo-Wan Nam; Hyun-Yi Park; Jong-Hyun Kim; Jin-Ho Seo; Nam-Soo Han; Byung-Woo Kim (Biotechnology Letters, 2001)

Biodegradable Polyester, Poly[α-(4-Aminobutyl)-l-Glycolic Acid], as a Non-Toxic Gene Carrier - Yong-Beom Lim; Sang-Oh Han; Han-Uk Kong; Yah Lee; Jong-Sang Park; Byeongmoon Jeong; Sung Wan Kim (Pharmaceutical Research, 2000)

A new class II rice chitinase, Rcht2, whose induction by fungal elicitor is abolished by protein phosphatase 1 and 2A inhibitor - Cha Young Kim; Sang Wan Gal; Mi Sook Choe; Sun Yong Jeong; Soo In Lee; Yong Hwa Cheong; Sang Hyoung Lee; Young Ju Choi; Chang-deok Han; Kyu Young Kang; Moo Je Cho (Plant Molecular Biology, 1998)

A Rapid DNA Extraction Method for RFLP and PCR Analysis from a Single Dry Seed - Hee Wan Kang; Yong Gu Cho; Ung Han Yoon; Moo Young Eun (Plant Molecular Biology Reporter, 1998)

Expression and secretion of Clostridium thermocellum endoglucanase A gene (celA) in different Saccharomyces cerevisiae strains - Dae-Kyun Chung; Dong-Ha Shin; Byung-Woo Kim; Jae-Kook Nam; In-Seob Han; Soo-Wan Nam (Biotechnology Letters, 1997)